Application of solid electrolyte interface (SEI) in anode of fluoride ion / shuttle battery

By using rare earth or alkaline earth metal anode, cathode of transition metal core-shell structure and liquid fluoride electrolyte in fluoride ion battery packs, and forming SEI layers, the difficulty of recharge and reaction kinetics of fluoride ion battery packs is solved at room temperature. Slow problem, achieving high energy density and long life battery packs.

CN113196536BActive Publication Date: 2025-02-11HONDA MOTOR CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN201980080679.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-03
Filing Date
2019-12-05
Publication Date
2025-02-11
Estimated Expiration
2039-12-05

AI Technical Summary

Technical Problem

Existing fluoride ion battery packs are difficult to recharge at room temperature, and the reaction kinetics are slow, affecting energy density and battery life.

Method used

The solid electrolyte phase interface (SEI) layer is formed to improve cell performance by using an anode containing rare earth metal or alkaline earth metal, a cathode with a transition metal core-shell structure, and a liquid fluoride electrolyte.

Benefits of technology

A fluorine ion battery pack that is reversible at room temperature is realized, which improves energy density and battery life, and solves the problem of slow reaction kinetics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003102078850000021
    Figure BDA0003102078850000021
  • Figure BDA0003102078850000161
    Figure BDA0003102078850000161
  • Figure BDA0003102078850000291
    Figure BDA0003102078850000291
Patent Text Reader

Abstract

The present disclosure relates to fluoride (F) ion batteries and F shuttle batteries comprising an anode having a solid electrolyte interface (SEI) layer, a cathode comprising a core-shell structure, and a liquid fluoride battery electrolyte. According to some aspects, the components therein enable discharge and recharge at room temperature.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to each of the following applications: U.S. Provisional Application No. 62 / 776,978, entitled “Room-Temperature Cycling of Metal Fluoride Electrodes: Liquid Electrolytes For High-Energy Fluoride Ion Cells”, filed on December 7, 2018; U.S. Provisional Application No. 62 / 775,690, entitled “Room-Temperature Cycling of Metal Fluoride Electrodes: Liquid Electrolytes For High-Energy Fluoride Ion Cells”, filed on December 5, 2018; and U.S. Provisional Application No. 62 / 863,114, entitled “Solid Electrolyte Interface Composition”, filed on June 18, 2019. Each of the foregoing applications is incorporated herein by reference in its entirety.

[0003] STATEMENT REGARDING FEDERALLY SPONSORED RESEARCH OR DEVELOPMENT

[0004] This invention was made with government support under Contracts DE-AC05-00OR22725 and DE-AC02-05CH11231 awarded by the U.S. Department of Energy (DOE). The government has certain rights in this invention.

[0005] Incorporated by Reference

[0006] Each of the following applications is incorporated herein by reference in its entirety: U.S. Patent Publication No. 2017 / 0062874A1 (U.S. Patent Application No. 15 / 228,876), entitled “Non-Aqueous Fluoride Salts, Solutions, and Their Uses,” filed on August 4, 2016; U.S. Patent Application No. 16 / 444,854, entitled “Electroactive Materials Modified With Molecular Thin Film Shell,” filed on June 18, 2019; U.S. Patent Application No. 15 / 844,079, entitled “Composite Electrode Materials for Fluoride-Ion Electrochemical Cells,” filed on December 15, 2019; and U.S. Patent Application No. 16 / 445,022, entitled “Nanostructural Designs for Electrode Materials of Fluoride Ion Batteries,” filed on June 18, 2019. Background Art

[0007] Fluoride ion batteries are a novel and underdeveloped alternative next generation energy storage technology. The energy density of fluoride ion batteries can be much higher than that of lithium ion batteries. Much of the ongoing research is focused on all-solid-state fluoride ion batteries, which are rechargeable to some extent at elevated temperatures. However, the slow reaction kinetics pose a major challenge to all-solid-state fluoride ion batteries. The reaction kinetics are better in liquid type fluoride ion batteries. However, this type of fluoride ion battery still faces many challenges, such as the lack of efficient, rechargeable electrolytes and reversible cathode and anode materials at room temperature. As the energy demand for electric vehicles, portable electronic devices and portable energy storage continues to grow, the need for advanced fluoride ion batteries is also growing. Summary of the invention

[0008] According to some aspects, the present disclosure relates to a fluoride (F) ion battery and a F shuttle battery, comprising: an anode comprising a rare earth metal or an alkaline earth metal (or a mixture of metals) and a solid electrolyte interphase layer; a cathode comprising a transition metal and a core-shell structure; and a liquid fluoride battery electrolyte. In some embodiments, the fluoride ion battery disclosed herein may be a fluoride (F) shuttle battery with multi-electron transfer. According to some aspects, the present disclosure relates to a dedicated anode for a fluoride ion battery, comprising a metal (e.g., Ce, La, and Ca) as an active anode material and having a solid electrolyte interphase (SEI) layer on the anode surface. In some embodiments, the SEI layer may comprise a fluorinated compound. In some embodiments, the SEI layer may comprise a chemical compound that is stable on the anode surface, such as a reaction derivative formed between a diazonium salt and the anode surface, wherein the diazonium salt has a structure of Formula I:

[0009]

[0010]

[0011] Wherein X can be, for example, -C(CH3)3, -OCH3, -NMe2, -NO2, or -CF3. The core-shell structures disclosed herein can be in various shapes or forms, the SEI layer can contain different adjustable chemical compounds, and the liquid fluoride electrolyte can provide reliable chemical stability. In some embodiments, the present disclosure relates to various methods of solid electrolyte interface (SEI) formation and various methods of manufacturing fluoride ion batteries and components thereof. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] The patent or application file contains at least one drawing executed in color. Copies of this patent or patent application publication with one or more color drawing(s) will be provided by the Office upon request and payment of the necessary fee.

[0013] Figure 1A The energy density of various types of battery packs is depicted.

[0014] Figure 1B Examples of suitable anode and cathode metals / materials are depicted.

[0015] Figure 2 is a schematic diagram of a fluoride ion electrochemical cell according to some aspects of the present disclosure.

[0016] Figure 3 Schematic diagram of a non-limiting solid electrolyte interface (SEI) layer on an anode that allows passage of ions but not electrons while being stable on the surface of the active material and current collector according to some aspects of the present disclosure.

[0017] Figure 4The reaction (free radical) mechanism of silane (FOTS) with the anode surface in SEI formation (solid electrolyte interface formation) according to some aspects of the present disclosure is illustrated.

[0018] Figure 5 The reaction (free radical) mechanism of the diazonium salt with the anode surface in SEI formation (solid electrolyte interface formation) according to some aspects of the present disclosure is illustrated.

[0019] Figure 6 The ratio between carbon atoms in the benzene ring of the diazonium salt molecule and calcium atoms from the electrode (i.e., the C / Ca ratio) and the ratio between fluoride ions in the diazonium salt and calcium atoms from the electrode (i.e., the F / Ca ratio) according to some aspects of the present disclosure are summarized.

[0020] Figure 7 To decompose tetraalkylammonium fluoride salts to form HF and HF2 under dry conditions - 's hint.

[0021] Figure 8 is a bar graph of voltage windows measured from linear sweep voltammograms of non-limiting examples of electrolyte solutions of the present disclosure.

[0022] Fig.9A Shown are the results from non-aqueous, F - - Data of room temperature conversion reactions on the surface of Ce anode materials cycled in a conducting liquid electrolyte. (A) Voltage curves of Ce anode collected during electrochemical charge and discharge in a three-electrode cell.

[0023] Fig. 9B pXRD patterns obtained for a Ce anode in its original state (black), after first charge or fluorination (red) and after first discharge or defluorination (blue) are shown. Asterisks indicate new peaks corresponding to CeF3.

[0024] Fig. 10A , Fig. 10B and Fig. 10C The solid electrolyte phase interface formation and the characterization of the anode materials are shown. Electrochemical grafting of FOTS additive (0.25 M) onto the Ce or Ca anode surface was achieved according to standard procedures, where electrochemical tests were performed in cyclic voltammetry ( Fig. 10A ) and electrochemical impedance spectroscopy studies ( Fig. 10B ) are carried out alternately. In the electrochemical grafting experiment ( Fig. 10C ) and then the formation of SEI layer on the Ce or Ca surface was confirmed by XPS analysis of the anode. Figures 10A-10C The data shown in were collected for SEI formation on Ca anodes.

[0025] Fig.11A It shows that in non-aqueous, F- -Room temperature performance of metal electrode materials for reversible cycling in conducting liquid electrolytes. Voltage curves of Ce with SEI layer formed by FOTS additive in 0.75M Np1F / BTFE. Fig.11A The upper right inset in FIG. 4 shows a more detailed view of the charging cycle.

[0026] Fig. 11B The pXRD patterns of Ce electrode in pristine state (top spectrum), Ce with SEI layer after first charge or fluorination in 0.75M Np1 / BTFE at room temperature (middle spectrum), and after first discharge or defluorination (bottom spectrum) are shown. Asterisks indicate new peaks corresponding to CeF3, which are attributed to metal fluorination after charge.

[0027] Fig. 12A and Fig. 12B An exemplary increase in the negative potential of an additive-grafted calcium anode in a BTFE-based electrolyte as determined by linear sweep voltammograms (LSV) is outlined: Fig. 12A )FH-grafted calcium anode in NpMe3NF-BTFE electrolyte; and ( Fig. 12B )FOTS-grafted calcium anode in Et3MeN·BF4-BTFE electrolyte.

[0028] Fig.13A , 13B and 13C outline exemplary XPS studies of FH SEI and FOTS SEI grafted on calcium anode surfaces: Fig.13A shows the XPS spectrum of FH SEI grafted on calcium anode; Fig. 13B shows the XPS spectrum of FOTSSEI grafted on the calcium anode; Fig. 13C The ratio between fluorine and calcium active surface material in the SEI layer (F / Ca) is shown for FH and FOTS.

[0029] Fig.14 An exemplary reduction in anode potential (V-window expansion) caused by a SEI layer and anode potentials of several non-limiting anode materials according to some aspects of the present disclosure are outlined.

[0030] Fig.15 The results were obtained by using 0.05 MF3CC6H4N2·BF4 (diazonium salt) additive in 0.1 M TMABF4 / BTFE at a scan rate of 1 mV / s from -4.5 V to -2.5 V (vs. Ag / Ag + ) to form an SEI on a Ce electrode by performing CV cycling at potentials between 10 and 10 . According to some aspects of the present disclosure, the SEI layer causes the expansion of negative potential observed during 20 cycles as shown by the blue arrows.

[0031] Fig.16A The charge (fluorination) / discharge (defluorination) of a Ce electrode having an SEI layer formed of the diazonium salt F3CC6H4N2·BF4. A discharge plateau is observed as indicated by the arrow.

[0032] Fig. 16B Figure 2 shows the pXRD patterns of the initial Ce anode, the Ce anode with SEI formed by the diazonium salt F3CC6H4N2·BF4, after fluorination, and defluorination. The formation of CeF3 after charging confirms the fluorination of Ce, which indicates that F - Ions can penetrate the SEI layer. Partial defluorination of CeF3 was observed after discharge, as some peaks of CeF3 decreased or disappeared.

[0033] Fig.17A The trimethylneopentylammonium fluoride (Np1F) is shown. 1 H NMR (nuclear magnetic resonance) spectrum. 1 H NMR(400MHz,CD3CN)δ3.34(2H,s,N + CH2C(CH3)3),3.26(9H,s,N + (CH3)3),1.18(9H,s,N + CH2C(CH3)3).

[0034] Fig. 17B The trimethylneopentylammonium fluoride (Np1F) is shown. 19 F NMR spectrum. 19 FNMR(376MHz,CD3CN)δ-74.29(s,F - ),-147.00(t,DF2 - ).

[0035] Fig.18A and Fig.18B The NMR spectrum of dimethyldineopentylammonium fluoride (Np2F) is shown. Fig.18A Shows 1 HNMR(300MHz,CD3CN,20℃)δ3.48(4H,s,N + (CH2C(CH3)3)2),3.34(6H,s,N + (CH3)2),1.19(18H,s,N + (CH2C(CH3)3)2). Fig.18B Shows 19 F NMR(282MHz,CD3CN,20℃)δ-72.87(s,F - ),-147.00(t,DF2 - ).

[0036] Fig.19A Figure 2 shows the pXRD characterization of the raw powder of the synthesized copper nanoparticles. α ) spectrum, the characteristic peaks of metallic copper are depicted (all peaks marked with squares).

[0037] Fig.19B TEM images of synthesized copper nanoparticles (diameter -50 nm) are shown.

[0038] Fig.19C pXRD characterization of the raw powder of as-synthesized core@shell nanoparticles (Cu@LaF3) is shown. The characteristic peaks of metallic copper (squares) and lanthanum trifluoride (circles) are depicted.

[0039] Fig.19D TEM images of pristine core-shell (Cu@LaF3 core-shell cathode material) nanoparticles are shown. The inset in the lower right corner shows a high-resolution TEM (HR-TEM) image of a thin LaF3 shell encapsulating a thicker Cu core.

[0040] Fig. 20A Shown are cyclic voltammograms of a Cu-LaF3 thin film electrode in 0.1 M TMAF / MPPy-TFSI for 10 cycles, obtained during the characterization of the Cu@LaF3 core-shell cathode material and its electrochemical cycling at room temperature.

[0041] Fig. 20B It is an overlay of Figures D and E and shows the X-ray photoelectron spectroscopy (XPS) depth profiling (nm) of the Cu-LaF3 thin film electrode in the pristine state (dashed line) and after charging (solid line) at stages characterizing the Cu@LaF3 core-shell cathode material and its electrochemical cycling at room temperature.

[0042] Fig. 20C A one-hour potential hold (3.12 V) of a Cu-LaF3 thin film electrode in 0.1 M TMAF / MPPy-TFSI is shown to ensure electrochemical fluorination.

[0043] Fig.20D The XPS depth profiling of the pristine Cu-LaF3 thin film electrode via x-ray photoelectron spectroscopy (XPS) is shown. (Angstroms per second)Ar + Etch rate. Use the etch rate to convert etch time (seconds) to sample depth (nanometers).

[0044] Fig.20E The XPS depth profiling of a fluorinated Cu-LaF3 thin film electrode via x-ray photoelectron spectroscopy (XPS) is shown. (Angstroms per second)Ar + Etch rate. Use the etch rate to convert etch time (seconds) to sample depth (nanometers).

[0045] Fig.21A for Figures 21B-21D Overlay and show linear sweep voltammograms collected for 0.75MNp1F in neat BTFE, BTFE:DME (3:2 vol %) and BTFE:TEGDME (3:2 vol %) using a scan rate of 1 mV / s (DME = 1,2-dimethoxyethane; TEGDME = bis[2-(2-methoxyethoxy)ethyl] ether) obtained during measurements of the physical and electrochemical properties of a non-aqueous, fluoride ion conducting liquid electrolyte (at 25°C).

[0046] Fig. 21B The linear sweep voltammogram of 0.75M Np1F in neat BTFE is shown. The linear regression analysis of the linear portion of the raw LSV data is shown (dashed line).

[0047] Fig. 21C Linear sweep voltammogram of 0.75M Np1F in BTFE:DME is shown. Linear regression analysis of the linear portion of the raw LSV data is shown (dashed line).

[0048] Fig.21D Linear sweep voltammogram of 0.75M Np1F in BTFE:TEGDME is shown. Linear regression analysis of the linear portion of the raw LSV data is shown (dashed line).

[0049] Fig. 22 The calculated F atoms are shown according to the H (or F) atoms bonded to the α-CX2 part of the solvent. - Comparison of radial distribution functions to understand the physical and electrochemical properties of non-aqueous, fluoride ion conducting liquid electrolytes (25°C) Calculations were performed using LAMMPS (Large Atomic / Molecular Massively Parallel Simulator) molecular dynamics simulations.

[0050] Fig.23A Shown are the partial charge distributions in the chemical structures of BTFE and diethylene glycol dimethyl ether solvents as determined via CHELPG (fitting electrostatic potential charges using a grid-based method) calculations on the B3LYP-D3 / def2-TZVP electron density.

[0051] Fig. 23B shows the quantum chemical calculations around F represented by the central sphere. - Simulated solvation shell of a BTFE molecule.

[0052] Fig.23C It shows that Np2 +Quantum chemical calculations of the cation (molecule with the central black outline) in BTFE. In the solvation sphere, Np2 + The distance between the cation atoms and the BTFE atoms is about Qualitatively, the CF3 group on BTFE is at Np2 + It seems to be most prevalent in solvated structures.

[0053] Fig.24A An example of the long-term stability of fluoride ionic liquid electrolytes is shown. 19 % F in Np1F / BTFE (upper panel, circles) and Np1F / PN (lower panel, squares) solutions measured by F NMR (without deuterated NMR solvents). - long-term monitoring.

[0054] Fig. 24B and Fig.24C An example of the long-term stability of fluoride ionic liquid electrolytes is shown. Np1F / PN (upper spectrum) and Np1F / BTFE (lower spectrum) when CD3CN NMR solvent is used and when no deuterated NMR solvent is used 1 H NMR ( Fig. 24B )and 19 F NMR ( Fig.24C ) Spectra comparison.

[0055] Fig.24D A control experiment is shown, which shows the Np1F dissolved in deuterated acetonitrile (d3-AN, top spectrum) or deuterated propionitrile (d5-PN, bottom spectrum). 1 H. 2 H and 19 F NMR spectrum.

[0056] Fig.25A and Fig.25B An Arrhenius analysis of a fluoride ionic liquid electrolyte is shown. Fig.25A The ion diffusion constant (D) from PFG-NMR is shown. Np+ +D F- ) of the Arrhenius diagram, and Fig.25B Shown are the ionic conductivities from AC impedance at temperatures ranging from 5 to 40°C (in 5°C increments) for each of the three electrolyte compositions investigated: 0.75M Np1F / BTFE (circles), 0.75M Np2F / BTFE (squares), and 0.75M Np1F / (3:1 BTFE:DME) (triangles).

[0057] Fig.26The Stokes radius (R) of the electrolyte ions in 0.75M Np1F / BTFE (left, α = 0.087) or 0.75M Np2F / BTFE (right, α = 0.108) is shown. 离子 ). Also shown is the degree of ion dissociation (α) as calculated during characterization of the physical and electrochemical properties (25° C.) of the non-aqueous, fluoride ion conducting liquid electrolyte (SD is ±0.003).

[0058] Fig.27A Representative schematics showing the external electron flow, electrolyte ion shuttling, and redox reactions occurring at the FIB electrodes during a charge or discharge cycle.

[0059] Fig.27B It shows that in non-aqueous, F - -Room-temperature performance of metal electrode materials for reversible cycling in conducting liquid electrolytes: electrochemical cycling data collected for Bi.

[0060] Fig.27C It shows that in non-aqueous, F - -Room temperature performance of reversibly cycled metal electrode materials in conducting liquid electrolytes: powder X-ray diffraction (pXRD) patterns obtained for Bi.

[0061] Fig.27D It shows that in non-aqueous, F - -Room temperature performance of metal electrode materials for reversible cycling in conducting liquid electrolytes: electrochemical cycling data collected for Pb.

[0062] Fig.27E It shows that in non-aqueous, F - - Room temperature performance of metal electrode materials for reversible cycling in conducting liquid electrolytes: Powder X-ray diffraction (pXRD) patterns obtained for Pb.

[0063] Fig.28A The voltage curve of the Cu cathode collected during electrochemical cycling in a three-electrode cell is shown. The three-electrode cell was assembled with a metal cathode (working electrode), a Pt wire (counter electrode), and an Ag rod (reference electrode) in AgOTf / MPPy-TFSI in the specified electrolyte, where IL = 0.1 M TMAF / MPPy-TFSI and BTFE = 0.1 M Np1F / BTFE. The voltage curve of the Cu cathode collected during electrochemical cycling in a three-electrode cell was shown. The voltage curve of the Cu cathode was collected during electrochemical cycling in a three-electrode cell. The voltage curve of the Cu cathode was calculated by adding an experimentally determined reference potential (4.12 V) relative to Ag. + The reference electrode potential of Ag is converted to that of Li + / Li potential.

[0064] Fig.28BPowder X-ray diffraction (pXRD) patterns obtained for a Cu cathode in its original state (top spectrum), after the first charge or fluorination (second from the top spectrum), and after the last discharge or defluorination (bottom spectrum) are shown. No CuF2 was observed (presumably due to the Cu 2+ dissolved into solution).

[0065] Fig.29A Representative EELS spectra showing the FK, La M and FK in the shell, interface and core regions of the fluorinated Cu@LaF3 core-shell cathode material sample are shown. 5,4 and Cu L 3,2 The upper left and upper right insets show the F K-absorption edge and Cu L absorption edge from the figure below, respectively. 3,2 - Absorbing edges.

[0066] Fig.29B Shown are averaged elemental percentage plots of Cu, La, and F obtained from 36 different EELS spectra, 12 each, from the shell, interface, and core regions of multiple fluorinated particles of the fluorinated Cu@LaF3 core-shell cathode material sample.

[0067] Fig.30 The average local density of fluorine ions in the SAM region at zero bias potential (ΔV=0) according to Example V is shown. <c>and the average distance between fluoride ions and the electrode <d>.

[0068] Fig.31A The mean force potential (PMF) for fluoride ion SAM intercalation at several electrode potentials according to Example V is shown.

[0069] Fig.31B The average local density of fluoride ions in the SAM region at several electrode potentials according to Example V is shown. <c>.

[0070] Fig.31C The average distance between fluoride ions and the electrode at several electrode potentials according to Example V is shown. <d>.

[0071] Fig.32A An all-atom configuration according to Example V is shown, illustrating the solvation of fluoride ions within the SAM region.

[0072] Fig.32B The cumulative number of atoms (F or H) around the fluoride ion according to Example V is shown as a function of the interatomic distance within the SAM region.

[0073] Fig.32C The partner hydrogen exchange rate τ of fluoride ions in the SAM region according to Example V is shown. -1 ex .

[0074] Fig.33 The rate τ of fluoride ion deintercalation from the SAM region at several electrode potentials according to Example V is shown. -1 de .

[0075] Fig.34 The distribution of solvation sites at the metal-SAM interface according to Example V is shown. Summary of the invention

[0077] The present disclosure relates to specific aspects of fluoride ion batteries, various components of fluoride ion batteries, methods of making fluoride ion batteries, and methods of using fluoride ion batteries, as well as various components and devices therein. Various aspects of the durability of the internal components of fluoride ion batteries when liquid non-aqueous fluoride electrolytes are employed to achieve room temperature rechargeable fluoride ion batteries will be disclosed herein.

[0078] Fluoride ion batteries offer new opportunities to increase the energy density of batteries compared to lithium ion batteries. While offering high energy density and the possibility of multiple charge transfers, the high reactivity of fluoride ions can bring many problems, such as dissolution of the anode and cathode and difficulty in defluorinating the anode material. Therefore, all-solid-state fluoride ion batteries using solid electrolytes have been studied, but the slow reaction kinetics require elevated temperatures for recharging. Liquid electrolytes containing fluoride ions in solution would provide faster kinetics and could provide recharging at room temperature, but the high reactivity of fluoride ions would result in short battery life. Fluoride-containing anions (F - ) in aqueous solution shows a rapid reaction of fluoride ions with water to form hydrofluoric acid (HF) and the complex ion HF2 - ( Figure 7 ). The formation of HF is highly corrosive and toxic. In addition, in electrochemical applications HF2 - The activity is much lower than that of F - , and in extreme cases may even be inactive. HF2 - It is also undesirable because it would evolve H2 at a potential below that of the targeted cathode reaction, thereby limiting the usable voltage window in electrochemical applications and potentially causing failure of the battery containing the electrolyte.

[0079] Non-aqueous F - The use of electrolyte solution can solve the problem of aqueous F - However, it has been demonstrated that non-aqueous F - Solutions are difficult to prepare at concentrations high enough to be usable (e.g., greater than or equal to 0.05 M). According to some aspects of the present disclosure, a liquid electrolyte suitable for a fluoride ion battery (FIB) may include a fluoride salt and a non-aqueous solvent, wherein the fluoride salt is at least partially present in a dissolved state. The fluoride salt may be a metal fluoride or a non-metal fluoride. The solvent may be an organic liquid or an ionic liquid, or a mixture of the two. In some embodiments, an electrolyte suitable for a FIB may include a composite electrolyte containing a fluoride salt, a polymer, and optionally an organic liquid, an ionic liquid, or a mixture of the two.

[0080] Metal fluoride electrolyte salts are generally not soluble in organic matter at concentrations > 0.05 M. Organic fluoride electrolyte salts, such as those with tetraalkylammonium (R4N + ) cations, may have improved solubility; however, due to F - To HF2 - Decomposition of easily occurs by elimination processes at elevated temperatures, so it is not easy to synthesize in a truly anhydrous form. Neopentyl-substituted (Np or 2,2-dimethylpropyl-)alkylammonium salts were tested in organic solvents for applications in fluoride ion batteries (e.g., solubility, durability) because the Np chain is both branched (to improve solubility) and lacks β-hydrogen (to inhibit decomposition on drying). After preliminary screening, for example, dry N,N,N-trimethyl-N-neopentylammonium fluoride (Np1F) and N,N-dimethyl-N,N-dineopentylammonium fluoride (Np2F) were synthesized in batches up to 100 g using an HF-titration procedure and both showed suitability for FIBs compared to tetramethylammonium fluoride (TMAF).

[0081] Various organic solvents provide different levels of electrolyte life. For example, BTFE (2,2,2-trifluoroethyl sulfone, bis(2,2,2-trifluoroethyl) ether) was found to provide a suitable voltage window ( Figure 8 ) and electrolyte life ( Figures 24A-24D ).

[0082] According to some aspects of the present disclosure, the liquid electrolyte for the FIB may include bis(2-methoxyethyl)ether, bis(2,2,2-trifluoroethyl)ether, N,N,N-trimethyl-N-neopentylammonium fluoride, N,N-dimethyl-N,N-dineopentylammonium fluoride, propionitrile, or a combination thereof. With a suitable electrolyte, the development of room temperature rechargeable FIBs also requires durable internal components, for example, due to the high energy density and high reaction potential of the FIB ( Figure 1A ).

[0083] According to some aspects of the present disclosure, the anode comprises an outer layer of a solid electrolyte interface (SEI) that extends the negative potential of the electrolyte and / or prevents dissolution of the anode metal to achieve reversible fluorination and defluorination of the anode material while allowing F - Transfer from electrolyte to anode ( Figure 3 ). Suitable compounds for forming SEI are disclosed herein, and Example 5 describes an example of the formation of SEI. Figure 1B Some examples of suitable anode metals are shown in .

[0084] According to some aspects, the outer SEI layer is covalently bonded to the anode metal. Figure 4 and Figure 5 A non-limiting example of a SEI connection is illustrated in FIG. The outer solid electrolyte phase interface layer may include CF3(CF2)5CH2, CF3(CF2)2CH2, p-tert-butylphenyl, p-methoxyphenyl, p-(dimethylamino)phenyl, p-nitrophenyl, p-trifluoromethylphenyl, or a combination thereof. In some embodiments, the outer solid electrolyte phase interface layer includes 1H,1H,2H,2H-perfluorooctyltriethoxysilane, 3,3,4,4,5,5,6,6,6-nonafluorohex-1-ene ( Figure 4 ), 4-tert-butylbenzene diazonium salt, 4-methoxybenzene diazonium salt, 4-(dimethylamino)benzene diazonium salt, 4-nitrobenzene diazonium salt, 4-trifluoromethylbenzene diazonium salt or a combination thereof, such as Figure 5 In some embodiments, the outer solid electrolyte interfacial layer can be a film on the anode and can include 4-tert-butylbenzene diazonium salt, 4-methoxybenzene diazonium salt, 4-(dimethylamino)benzene diazonium salt, 4-nitrobenzene diazonium salt, 4-trifluoromethylbenzene diazonium salt, or a combination thereof, and also contains a salt counter anion. According to some aspects, the counter anion can include an organic soluble counter ion. Non-limiting examples of counter anions that can be used according to the present disclosure include BF4 - 、F - , Cl - PF6 - CF3SO3 - 、[(CF3SO2)2N] - and combinations thereof.

[0085] In addition to various electrolyte and anode components of a fluoride ion battery (FIB), a cathode of the FIB is also disclosed. According to some aspects, such as Figure 1B As exemplified in , the cathode metal further comprises a shell. The cathode metal may, for example, comprise a transition metal. The transition metal may have certain dimensions at the nanoscale to improve, for example, efficiency and charge transfer. In some embodiments, the cathode may contain core-shell particles having a transition metal core and a shell at least partially surrounding the transition metal core, the shell being in contact with the electrolyte. Fig.19B Non-limiting examples of suitable copper core particles are shown in . It should be understood that, as used herein, the expression "at least partially surrounding" can refer to partial coverage (e.g., about 70%, optionally about 80%, optionally about 90%, and optionally about 95% coverage) or complete coverage (e.g., greater than about 95%, optionally greater than about 96%, optionally greater than about 97%, optionally greater than about 98%, optionally greater than about 99%, and optionally about 100% coverage).

[0086] In some embodiments, the transition metal core may comprise copper and the shell may comprise LaF3. For example, Fig.19D A LaF3 shell surrounding a copper core particle is illustrated. According to some aspects, the transition metal core may have at least one dimension less than or equal to about 20 nm. In some embodiments, the shell comprises a thickness of about 2 nm to about 5 nm.

[0087] According to some aspects, disclosed herein is a method for making a cathode for a fluoride ion battery, the method comprising providing a solid transition metal and treating the solid transition metal with lanthanum and fluorine to form a LaF3 shell at least partially surrounding the solid transition metal. According to some aspects, the solid transition metal may include bismuth, lead, copper, or a combination thereof. The treatment may include dispersing the solid transition metal in an aqueous solution of hydrazine hydrate and contacting the solid transition metal with an aqueous solution of lanthanum ions and fluoride ions. The aqueous solution of lanthanum ions and fluoride ions may include lanthanum nitrate hexahydrate and sodium fluoride. In some embodiments, the treatment may include radio frequency sputtering LaF3 onto the solid transition metal.

[0088] Another example method of making a cathode for a fluoride ion battery as disclosed herein may include a method as described in US Patent Application No. 15 / 844,079, the disclosure of which is incorporated herein by reference in its entirety.

[0089] Core-shell particles having a transition metal core and a shell at least partially surrounding the transition metal core can be applied to a metal cathode or can be loaded by various means to be utilized in a FIB. According to some aspects, agglomerates of transition metal cores and a shell at least partially surrounding the transition metal core are formed as suitable cathodes.

[0090] According to some aspects, the core-shell particles with a transition metal core and a shell at least partially surrounding the transition metal core can form a paste, can be combined with other compounds, can be dried, can be shaped, can be agglomerated, or can be utilized by any means known in the art. In some embodiments, the core-shell particles with a transition metal core and a shell at least partially surrounding the transition metal core can be made into a paste together with poly (vinylidene fluoride) PVDF and / or SP (Super P carbon black), pressed into a stainless steel mesh, and dried under vacuum to assemble the electrode. Accordingly, the electrolyte, anode and cathode disclosed herein can realize room temperature rechargeable FIB and its manufacturing method.

[0091] According to some aspects, the present disclosure relates to a fluoride ion battery (FIB), comprising: a liquid electrolyte with fluoride ions; an anode containing an alkaline earth metal, a rare earth metal, or a combination thereof and having an outer solid electrolyte phase interface layer in contact with the electrolyte; and a cathode containing core-shell particles, the core-shell particles having a transition metal core and a shell at least partially surrounding the transition metal core, the shell being in contact with the electrolyte or containing a transition metal having an optimized nanostructure (≤20 nm in one direction) in a molecular soft shell-surrounding manner. Non-limiting examples of optimized nanostructures include those described in U.S. Patent Application No. 16 / 445,022, the disclosure of which is incorporated herein by reference in its entirety.

[0092] In some embodiments, the fluoride ion batteries disclosed herein may be where the alkaline earth metal is calcium and the rare earth metal is selected from cerium and lanthanum. In some embodiments, the fluoride ion batteries disclosed herein may be where the transition metal core comprises bismuth, lead, copper, or a combination thereof.

[0093] According to some aspects, disclosed herein is a method for preparing a solid electrolyte interface (SEI) on an anode for a fluoride ion battery, the method comprising: 1) providing a liquid electrolyte comprising an additive; providing a working electrode in contact with the electrolyte, the working electrode comprising an alkaline earth metal, a rare earth metal, or a combination thereof; providing a counter electrode in contact with the electrolyte; and applying a potential cycle (cyclic voltammetry (CV)) between a first potential and a second potential to the working electrode for a plurality of cycles until the additive forms an outer solid electrolyte interface layer on the working electrode, wherein the second voltage potential is higher than the first voltage potential. In some embodiments, the working electrode may comprise calcium, cerium, lanthanum, or a combination thereof; 2) maintaining the potential on the working electrode constant at a certain voltage for a certain period of time, which may cause the additive to decompose or graft to form a SEI layer on the surface of the working electrode; 3) immersing the working electrode in a solution / electrolyte containing the additive; and / or 4) if the additive is F - reaction, the working electrode is pretreated in an electrolyte containing the additive, and the pretreated electrode is then transferred to an electrochemical cell for battery testing.

[0094] In some embodiments, relative to Li / Li + , the first potential may be about -0.8 V and the second potential may be about +0.7 V, the number of cycles may be up to five times, and the additive may include 1H,1H,2H,2H-perfluorooctyltriethoxysilane, 3,3,4,4,5,5,6,6,6-nonafluorohex-1-ene, or a combination thereof.

[0095] In one example of the diazonium salt SEI formation method, a preliminary test electrolyte containing 0.1M triethylmethylammonium tetrafluoroborate (TMABF4) in BTFE can be prepared. The calcium plate can be scrubbed with sandpaper and cut into strips of approximately 2.5mm×2.5mm for use as a working electrode. The calcium working electrode and electrolyte can be installed into a test device together with a platinum counter electrode. The test device can be purged with argon for 30 minutes. An initial EIS measurement can be performed by performing 5 CV cycles between -1V and 0.8V (relative to Li) to obtain a baseline for the cell (scan rate: 1mV / s). 0.05M of diazonium salt can be added to the cell electrolyte. In these experiments, all 0.05M may not be dissolved and are likely to be saturated at lower concentrations. The test device can be purged with argon for 30 minutes. 20 CV cycles are performed between -1.0V and 0.8V (relative to Li). EIS measurements can be performed every 5 cycles. After completion, the electrolyte and calcium samples can be retained for analysis.

[0096] In some embodiments, relative to Li / Li + , the first potential may be about -1.0V and the second potential may be about +0.8V (the potential range may vary depending on the selected additive), the number of cycles may be up to 20 times, and the additive may include 4-tert-butylbenzene diazonium salt, 4-methoxybenzene diazonium salt, 4-(dimethylamino)benzene diazonium salt, 4-nitrobenzene diazonium salt, 4-trifluoromethylbenzene diazonium salt and / or variations and / or combinations thereof. As used herein, the term "variation" refers to a compound as described herein having different substituent positions. For example, variations of 4-tert-butylbenzene diazonium salt may include, but are not limited to, 2-tert-butylbenzene diazonium salt, 2,3-tert-butylbenzene diazonium salt, and 3,4,5-tert-butylbenzene diazonium salt.

[0097] The present disclosure is not limited to the combination of elements of the FIB illustrated herein. For example, various anodes and cathodes disclosed herein can be combined with other components for various battery packs. For example, any electrolyte suitable for FIB can be used in combination with the anode and cathode disclosed herein. Liquid electrolyte salts suitable for FIB can contain complex ions in combination with fluoride anions. The cations may have organic groups, such as alkylammonium, alkylphosphonium or alkylsulfonium substances, or may be composed of metal-organic or metal coordination complex primitives such as metallocene species. Solvents available for such liquid electrolyte salts may include non-aqueous solvents (here referred to as "organic") capable of dissolving the above-mentioned fluoride salts at a molar concentration of 0.01M and above, preferably at a concentration between 0.1 and 3M. Examples of such solvents include acetone, acetonitrile, benzonitrile, 4-fluorobenzonitrile, pentafluorobenzonitrile, triethylamine (TEA), diisopropylethylamine, 1,2-dimethoxyethane, ethylene carbonate, propylene carbonate (PC), γ-butyrolactone, dimethyl carbonate, diethyl carbonate (DEC), ethyl methyl carbonate, methyl propyl carbonate, tetrahydrofuran, 2-methyltetrahydrofuran, nitromethane, benzene, toluene, chloroform, dichloromethane, 1,2-dichloroethane, dimethyl sulfoxide, sulfolane, N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMA), carbon disulfide, ethyl acetate, methyl butyrate, n-propyl acetate, methyl propionate, methyl formate, 4- Methyl-1,3-dioxolane, pyridine, methyl isobutyl ketone, methyl ethyl ketone, hexamethylphosphoramide, hexamethylphosphortriamide, 1-methyl-2-pyrrolidone, 2-methoxyethyl acetate, trimethyl borate, triethyl borate and substituted derivatives thereof, and sulfones such as ethyl methyl sulfone, trimethylene sulfone, 1-methyltrimethylene sulfone, ethyl sec-butyl sulfone, ethyl isopropyl sulfone (EIPS), 3,3,3-trifluoropropyl methyl sulfone, 2,2,2-trifluoroethyl sulfone, bis(2,2,2-trifluoroethyl) ether (BTFE), glycol dimethyl ethers (e.g., diethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether), 1,2-dimethoxyethane (DME) and mixtures thereof. In certain embodiments, room temperature ionic liquid materials or ionic liquids that remain liquid at temperatures below 200 degrees Celsius (such as those described in "Electrochemical Aspects of Ionic Liquids", E. Ohno ed., Wiley Interscience, New York, 2005) may be used.These may include ionic liquids that will remain liquid at temperatures below 100 degrees Celsius, such as 1-methyl 1-propylpiperidinium bis(trifluoromethanesulfonyl)imide (MPPTFSI), butyltrimethylammonium bis(trifluoromethanesulfonyl)imide (BTMATFSI), and 1-butyl 1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide (BMPTFSI) and their fluoroalkylphosphate (FAP) anion derivatives (e.g., MPPFAP), where the FAP is a hydrophobic anion such as tris(pentafluoroethyl)trifluorophosphate, all of which, alone or in combination, are useful solvents.

[0098] In some embodiments, the electrolyte suitable for FIB may include the composition disclosed above, wherein a fluoride ion complexing material is added, such as an anion receptor, a cation complexing material, such as a crown ether, or a combination of the two. Suitable anion receptors include materials such as boron, aluminum, ammonium, H-bond donors or similar groups that can bind fluoride anions, including azaethers and alkyl and aryl boron and borate complexes, such as those described in McBreen et al., J. Power Sources, 2000, 89, 163 and West et al., J. Electrochem. Soc., 154, A929 (2007), and boroxine species, such as those described in Nair et al., J. Phys. Chem. A, 113, 5918 (2009), all of which are incorporated herein by reference. In particular, tris(hexafluoroisopropyl)borate, tris(pentafluorophenyl)borane and all possible positional isomers of difluorophenylboroxine (DFB), trifluorophenylboroxine, bis(trifluoromethyl)phenylboroxine, bis(trifluoromethyl)phenylboroxine and fluoro(trifluoromethyl)phenylboroxine may be used.

[0099] According to some aspects, the present disclosure relates to a dedicated anode for a fluoride ion battery, which comprises a metal (e.g., Ce, La, and Ca) as an active anode material and has a solid electrolyte interface (SEI) layer on the surface of the anode. In some embodiments, the SEI layer may comprise a fluorinated compound. According to some aspects, such as Figure 6 As shown in FIG. 1 , the layer on the anode surface has various properties depending on the nature of the compounds within the layer. In some embodiments, the SEI layer may include chemical compounds that are stable on the anode surface, such as a covalent reaction ( Figure 5 ), the diazonium salt has the structure of formula I:

[0100]

[0101] wherein X may be, for example, -C(CH3)3, -OCH3, -NMe2, -NO2 or -CF3.

[0102] As used herein, the terms "uniform", "uniform size", and "uniform shape" are defined as remaining the same in all cases and at all times; unchanged in form or characteristics; with minimal or defined variations given the same reactants and the same reaction conditions. The aspect ratio of a shape is defined as the ratio of length to width or length to height, with a sphere having an aspect ratio of 1, and deviations from a spherical shape being represented by an aspect ratio (length / width or length / height) that is not 1. The aspect ratio of the shapes described herein may be about 1 ± 90%, 1 ± 80%, 1 ± 70%, 1 ± 60%, 1 ± 50%, 1 ± 40%, 1 ± 30%, 1 ± 20%, 1 ± 10%, 1 ± 5%, 1 ± 2.5, or 1 ± 1%.

[0103] As used herein, the term "catalyst" refers to a component that directs, stimulates, or accelerates a chemical reaction, such as the reaction of an electrochemical cell.

[0104] The present disclosure also relates to systems or devices comprising components, electrolytes, and nanostructures prepared according to the methods described herein. The present disclosure also relates to methods of using batteries and components prepared according to the methods described herein.

[0105] Using a simple and robust liquid electrolyte with high fluoride ion conductivity and a wide voltage window, the embodiments and examples disclosed herein demonstrate reversible electrochemical cycling of metal fluoride electrodes at room temperature, where F - The non-metallic cations are active shuttle ions. These examples and results allow the FIB to be operated at room temperature.

[0106] In the current disclosure, the terms "fluoride ion shuttle battery," "fluoride ion battery," "fluoride ion electrochemical cell," and "FIB" are interchangeable.

[0107] As used herein, the term "about" is defined as close to, as understood by one of ordinary skill in the art. In a non-limiting embodiment, the term "about" is defined as within 10%, preferably within 5%, more preferably within 1%, and most preferably within 0.5%.

[0108] "Inert atmosphere" refers to a gaseous mixture containing little or no oxygen and comprising an inert or non-reactive gas or a gas that has a high threshold before it reacts. The inert atmosphere can be, but is not limited to, molecular nitrogen or an inert gas such as argon or a mixture thereof. Examples of inert gases that can be used according to the present disclosure include, but are not limited to, gases comprising helium (He), radon (Rd), neon (Ne), argon (Ar), xenon (Xe), nitrogen (N), and combinations thereof.

[0109] A "reducing agent" is a substance that causes the reduction of another substance while it itself is oxidized. Reduction refers to the chemical substance gaining one or more electrons, while oxidation refers to the chemical substance losing one or more electrons.

[0110] A "metal salt" is an ionic complex in which the one or more cations are one or more positively charged metal ions, and the one or more anions are one or more negatively charged ions. "Cation" refers to an ion with a positive charge, and "anion" refers to an ion with a negative charge. In a "metal salt" according to the present disclosure, the anion can be any negatively charged chemical species. The metal in the metal salt according to the present disclosure can include, but is not limited to, alkali metal salts, alkaline earth metal salts, transition metal salts, aluminum salts or post-transition metal salts, and hydrates thereof.

[0111] An "alkali metal salt" is a metal salt wherein the metal ion is an alkali metal ion or a metal from Group I of the Periodic Table of the Elements, such as lithium, sodium, potassium, rubidium, cesium or francium.

[0112] An "alkaline earth metal salt" is a metal salt wherein the metal ion is an alkaline earth metal ion or a Group II metal of the Periodic Table of the Elements, such as beryllium, magnesium, calcium, strontium, barium or radium.

[0113] "Transition metal salts" are metal salts in which the metal ion is a transition metal ion or a metal in the d-block of the periodic table, including the lanthanides and actinides. Transition metal salts include, but are not limited to, salts of scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, yttrium, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, silver, cadmium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, hafnium, tantalum, tungsten, rhenium, osmium, iridium, platinum, gold, mercury, actinium, thorium, protactinium, uranium, neptunium, plutonium, americium, curium, berkelium, californium, einsteinium, fermium, mendelevium, nobelium, and lawrencium.

[0114] A "late transition metal salt" is a metal salt wherein the metal ion is a late transition metal ion such as gallium, indium, tin, thallium, lead, bismuth or polonium.

[0115] A "halide salt" is an ionic complex wherein the one or more anions are one or more halide ions, including but not limited to one or more fluoride ions, one or more chloride ions, one or more bromide ions, and one or more iodide ions. A "fluoride salt" is an ionic complex wherein the one or more anions are one or more fluoride ions. According to the present disclosure, the cation of a halide salt or fluoride salt can be any positively charged chemical species.

[0116] "Metal fluoride" is an ionic complex wherein the cation is one or more metal ions and the one or more anions are one or more fluoride ions. According to some aspects of the present disclosure, the one or more metal salts and the fluoride salt will react to produce a metal fluoride shell around the metal nanoparticle core. Similarly, "metal halide" is an ionic complex wherein the cation is one or more metal ions and the one or more anions are one or more halide ions.

[0117] "Fluoride-containing" salts are ionic complexes in which the one or more anions contain fluoride ions but are not limited to only fluoride ions. Alternatively, "fluoride-containing" salts include ionic complexes in which the one or more anions contain fluoride ions themselves complexed with other ions or atoms. "Fluoride-containing" salts suitable for use in aspects of the present disclosure include those known to those of ordinary skill in the art, including but not limited to fluoride salts, non-metallic fluoride anions such as tetrafluoroborate and hexafluorophosphate, and oxyfluoride salts. In some aspects of the present disclosure, fluoride-containing salts may include quaternary ammonium fluorides and fluorinated organic compounds. According to some aspects of the present disclosure, the metal salt and the fluoride-containing salt will react to produce a fluoride-containing shell around the metal nanoparticle core.

[0118] The term "electrode" refers to an electrical conductor in which ions and electrons are exchanged with an electrolyte and an external circuit. In this specification, "positive electrode" and "cathode" are used synonymously and refer to an electrode with a higher electrode potential (i.e., higher than the negative electrode) in an electrochemical cell. In this specification, "negative electrode" and "anode" are used synonymously and refer to an electrode with a lower electrode potential (i.e., lower than the positive electrode) in an electrochemical cell. Cathode reduction refers to the acquisition of one or more electrons by a chemical substance, while anodic oxidation refers to the loss of one or more electrons by a chemical substance. The positive and negative electrodes of the present invention can be provided in a range of available configurations and form factors known in the field of electrochemistry and battery science, including thin electrode designs, such as thin film electrode configurations.

[0119] The term "electrochemical cell" refers to a device and / or device component that converts chemical energy into electrical energy or vice versa. An electrochemical cell has two or more electrodes (e.g., a positive electrode and a negative electrode) and an electrolyte, wherein electrode reactions occurring on the electrode surfaces result in a charge transfer process. Electrochemical cells include, but are not limited to, primary batteries, secondary batteries, and electrolytic systems.

[0120] The term "electrolyte" refers to an ionic conductor that can be in a solid, liquid (most commonly), or more rarely in a gaseous state (eg, plasma).

[0121] The term "anhydrous" refers to compositions, including salts, such as fluoride salts, that are substantially free of water. In one embodiment, for example, an anhydrous fluoride salt is provided, characterized in that the amount of water is less than 1000 parts per million (ppm), and in some embodiments less than 100 parts per million (ppm). In one embodiment, for example, a method of preparing a solution containing fluoride ions is provided, wherein a fluoride salt as disclosed herein is provided in an anhydrous form and at least partially dissolved in one or more non-aqueous solutions.

[0122] The term "β-carbon" or "β-carbon" refers to a carbon atom that is separated from a target atom, group, functional group or other moiety by one carbon. In certain embodiments, the target functional group is a quaternary alkylammonium functional group and the β-carbon is the second carbon from the alkylammonium functional group.

[0123] It will be appreciated that the fluoride ion battery pack is suitable for a wide range of primary or rechargeable applications, including but not limited to vehicle traction batteries (electric vehicles (EV), hybrid electric vehicles (HEV) and plug-in hybrid electric vehicles (PHEV)) or vehicle starter or ignition batteries. The FIB system may be a usable stationary battery pack for emergency power, local energy storage, starter or ignition, remote relay station, communication base station, uninterruptible power supply (UPS), spinning reserve, peak regulation or load balancing or other grid power storage or optimization applications. Small or micro battery pack applications are covered, including watch batteries, implantable medical device batteries or sensing and monitoring system batteries (including gas or electricity meters), as well as other portable applications such as flashlights, toys, power tools, portable radios and televisions, mobile phones, portable cameras, laptops, tablets or PDAs, portable instruments, cordless devices, wireless peripherals or emergency beacons. Military or extreme environment applications are also possible, including use in satellites, munitions, robots, unmanned aerial vehicles or for military emergency power or communications.

[0124] Although the various aspects described herein have been described in conjunction with the exemplary aspects summarized above, various alternatives, modifications, variations, improvements and / or substantial equivalents, whether known or currently or possibly unforeseeable, will be apparent to a person having at least ordinary skill in the art. Accordingly, the example aspects as set forth above are intended to be illustrative and not limiting. Various changes may be made without departing from the spirit and scope of the present disclosure. Therefore, the present disclosure is intended to cover all known or later developed alternatives, modifications, variations, improvements and / or substantial equivalents.

[0125] Thus, the claims are not intended to be limited to the aspects shown herein, but are to be given the full scope consistent with the language of the claims, wherein reference to an element in the singular is not intended to mean "one and only one," but rather "one or more," unless explicitly so stated. All structural and functional equivalents to the elements of the various aspects described throughout this disclosure that are known or later come to be known to one of ordinary skill in the art are expressly incorporated herein by reference and are intended to be covered by the claims. Furthermore, nothing disclosed herein is intended to be dedicated to the public regardless of whether such disclosure is explicitly recited in the claims. No claim element should be construed as a means plus function unless an element is explicitly recited using the expression "means for..."

[0126] In addition, the word "example" is used herein to mean "serving as an example, instance, or illustration." Any aspect described herein as an "example" is not necessarily to be construed as preferred or advantageous over other aspects. Unless specifically stated otherwise, the term "some" refers to one or more. Combinations such as "at least one of A, B, or C," "at least one of A, B, and C," and "A, B, C, or any combination thereof" include any combination of A, B, and / or C, and may include multiples of A, multiples of B, or multiples of C. Specifically, combinations such as "at least one of A, B, or C," "at least one of A, B, and C," and "A, B, C, or any combination thereof" may be only A, only B, only C, A and B, A and C, B and C, or A and B and C, wherein any such combination may contain one or more members of A, B, or C. The content disclosed herein is not intended to be dedicated to the public, regardless of whether such disclosure is explicitly recited in the claims.

[0127] The examples are presented to provide those of ordinary skill in the art with a complete disclosure and description of how to make and use the invention and are not intended to limit the scope of what the inventors regard as their invention nor to represent that the experiments below are all or the only experiments performed. Efforts have been made to ensure accuracy with respect to numbers used (e.g., amounts, dimensions, etc.), but some experimental errors and deviations should be accounted for.

[0128] Furthermore, all references throughout this application, such as patent documents, including issued or granted patents or equivalents; patent application publications; non-patent literature documents or other original materials; are hereby incorporated by reference in their entirety as if individually incorporated by reference.

[0129] This detailed description uses examples to present the present disclosure, which includes preferred aspects and variations, and also enables any person skilled in the art to implement the disclosed aspects, including making and using any device or system and performing any incorporated method. The patentable scope of the present disclosure is defined by the claims and may include other implementations that occur to those skilled in the art. If such other implementations have structural elements that are not different from the literal language of the claims, or if they include equivalent structural elements that are not substantially different from the literal language of the claims, they are intended to be within the scope of the claims. A person of ordinary skill in the art may mix and match aspects of the various embodiments described and other known equivalents for each such aspect to construct additional embodiments and techniques according to the principles of the present application.

[0130] Although the various aspects described herein have been described in conjunction with the exemplary aspects summarized above, various substitutions, modifications, variations, improvements and / or substantial equivalents, whether known or currently or possibly unforeseeable, will be apparent to a person having at least ordinary skill in the art. Accordingly, the example aspects as set forth above are intended to be illustrative and not limiting. Various changes may be made without departing from the spirit and scope of the present disclosure. Therefore, the present disclosure is intended to cover all known or later developed substitutions, modifications, variations, improvements and / or substantial equivalents.

[0131] Unless explicitly stated otherwise, reference to an element in the singular is not intended to mean "one and only one," but rather "one or more." All structural and functional equivalents to the elements of the various aspects described throughout this disclosure that are known or later come to be known to those of ordinary skill in the art are expressly incorporated herein by reference. Furthermore, the content disclosed herein is not intended to be dedicated to the public.

[0132] In addition, the word "example" is used herein to mean "serving as an example, instance, or illustration." Any aspect described herein as an "example" is not necessarily to be construed as preferred or advantageous over other aspects. Unless specifically stated otherwise, the term "some" refers to one or more. Combinations such as "at least one of A, B, or C," "at least one of A, B, and C," and "A, B, C, or any combination thereof" include any combination of A, B, and / or C, and may include multiples of A, multiples of B, or multiples of C. Specifically, combinations such as "at least one of A, B, or C," "at least one of A, B, and C," and "A, B, C, or any combination thereof" may be only A, only B, only C, A and B, A and C, B and C, or A, B, and C, wherein any such combination may contain one or more members of A, B, or C.

[0133] As used herein, the terms "highly pure" and "high purity" are defined as about 98-100%, 99-100%, 99.9-100%, 99.99-100%, or 99.999%-100% pure.

[0134] In this article, the numerical ranges mentioned by endpoints (e.g., 50 mg to 600 mg, between about 100 and 500 ° C, between about 1 minute and 60 minutes) include all numbers included in the range, such as between about 20 minutes and 40 minutes include all numerical values ​​of 21, 22, 23 and 24, such as between about 20 minutes and 40 minutes include 21, 22, 23 and 24 as endpoints in the specified range. Thus, for example, depending on the starting materials used, the specific application, the specific embodiment or the limitations of the claims, if necessary, the ranges 22-36, 25-32, 23-29, etc. are also ranges whose endpoints are included in the range 20-40. The examples and methods disclosed herein demonstrate that the described ranges are included in every point in the range, because different results or products can be obtained after changing one or more reaction parameters. In addition, the methods and examples disclosed herein describe various aspects of the disclosed ranges and the effects of changing the ranges individually or in combination with other mentioned ranges. Example

[0135] All compounds and solvents were purchased from Sigma-Aldrich, Alfa Aesar, TCI (Tokyo Chemical Industry Co., Ltd.) America, Strem and / or Fisher and used as received. NMR solvents were purchased from Cambridge Isotope Laboratories, Inc. Anhydrous diethyl ether was obtained by elution through a solvent column drying system and degassed with argon before use. Solvents for solvent screening and electrolyte preparations with dried fluoride salts were prepared in a dry room or argon-filled glove box with The solvent was dried over 100 angstroms of molecular sieves. The H2O content (ppm) was monitored by Karl Fisher titration until the solvent was anhydrous (H2O ≤ 16 ppm). The electrode materials used included: bismuth foil (Alfa Aesar, 1 mm thick, 99.999%), lead foil (Alfa Aesar, 0.1 mm thick, 99.998%), cerium foil (Alfa Aesar, 0.62 mm thick, 99.9%), calcium foil (American Elements, 2 mm thick, 99.9%), Super P carbon black (SP; MTI Corporation, TIMCALGraphite&carbon Super P, conductive carbon black) and poly(vinylidene fluoride) (PVDF; Alfa Aesar).

[0136] Example 1: Fluoride Salt Synthesis (Np1F, Two Steps)

[0137] Trimethylneopentylammonium iodide was prepared by adding potassium carbonate (94.1 g, 681 mmol, 2.67 equiv) to a 1 L conical flask containing a magnetically stirred mixture of iodomethane (51 mL, 819 mmol, 3.21 equiv) and neopentylamine (30 mL, 255 mmol, 1.0 equiv) in anhydrous ethanol (400 mL). After magnetic stirring at room temperature for 21 hours, the mixture was suspended in ethanol (1.25 L), filtered, and the solvent removed in vacuo. The resulting solid was then suspended in dichloromethane (4 L) and filtered. The solvent was again removed in vacuo and the solid was recrystallized from isopropanol (450 mL). According to 1 H NMR, the crystals contained 1.6 mol% isopropanol. Removal of this trace solvent was achieved by dissolving it in water (55 mL) and washing with hexane (3 x 50 mL). Drying in vacuo gave 48.53 g of a white solid (74%). 1 H-NMR(300MHz,CD3CN)δ3.38(2H,s,N + CH2C(CH3)3),3.21(9H,s,N + (CH3)3),1.17(9H,s,N + CH2C(CH3)3). 13 C-NMR (126MHz, CDCl3) δ76.71, 56.03, 33.73, 30.16. HRMS(EI)C8H 20 N[H + ] Calculated value: 130.16; Measured m / z: 130.1596.

[0138] Trimethylneopentylammonium fluoride was prepared using a procedure adapted from the literature. To a solution of trimethylneopentylammonium iodide (10.772 g, 41.9 mmol, 1 eq) in deionized water (225 mL) was added silver oxide (14.559 g, 62.8 mmol, 1.5 eq) in a 500 mL round bottom flask covered with aluminum foil. After stirring for 1 hour, quantitative ion exchange of iodide with hydroxide was obtained, as evidenced by the absence of precipitation after adding an aliquot to a solution of silver nitrate in concentrated hydrochloric acid. The suspension was filtered and immediately titrated with aqueous hydrofluoric acid (0.5 wt %). HF was added dropwise and the titration was stopped at pH 7.96 (calculated endpoint = 8.08). Most of the water was removed under reduced pressure at 60°C. The solution was further dried by azeotroping with reference grade isopropanol (×3) at 35°C. To remove traces of silver residues, the solution was filtered (25 mm wheel filter, 0.45 μm PTFE membrane). The solution was transferred to a sidearm round bottom flask and residual water was removed by azeotroping with dry isopropanol (×5) under high vacuum (~50 mTorr) at 100° C. for five days until Np1F remained a white powder, according to 19 FNMR, its F - A single peak appears at -75 ppm downfield (in contrast, DF2 - Normalized to -147 ppm). 1 H-NMR(400MHz,CD3CN)δ3.34(2H,s,N + CH2C(CH3)3),3.26(9H,s,N + (CH3)3),1.18(9H,s,N + CH2C(CH3)3). 13 C-NMR (100MHz, CD3CN) δ76.35, 54.96, 33.41, 29.65. 19 F-NMR(376MHz,CD3CN)δ-74.29(s,F - ),-147.00(t,DF2 - ). 1 H NMR and 19 F NMR spectra Fig.17A and Fig. 17B Shown in.

[0139] Example 2: Fluoride Salt Synthesis (Np2F, Five Steps)

[0140] Preparation of N-(2,2-dimethylpropyl)-2,2-dimethylpropionamide. A 100 mL round-bottom flask equipped with a stir bar was charged with neopentylamine (10 mL, 85.5 mmol, 1.23 equiv), triethylamine (12 mL, 85.5 mmol, 1.23 equiv) and chloroform (70 mL) and cooled to 0 °C. Pivaloyl chloride (8.6 mL, 69.5 mmol, 1 equiv) was added dropwise and the resulting solution was refluxed (70 °C) for 4 h. After cooling to room temperature, the organic layer was rinsed with deionized water (3×), brine (1×), dried over sodium sulfate, and filtered. The solvent was removed in vacuo to give an orange solid (11.4 g, 96% yield). 1 H-NMR (300MHz, CDCl3, 20℃) δ5.66(1H,bs,O=CNH), 3.05(2H,d,NCH2C(CH3)3), 1.21(9H,s,O=CC(CH3)3), 0.90(9H,s,NCH2C(CH3)3). 13 C-NMR (126MHz, CDCl3) δ178.32, 50.32, 38.93, 32.09, 27.77, 27.26. HRMS(EI)C 10 H 21 NO[H + ]Calculated value: 172.2882; measured m / z: 172.1700.

[0141] Preparation of N-(2,2-dimethylpropyl)-2,2-dimethylpropane-1-amine. In a flame-dried three-necked flask equipped with a stir bar, lithium aluminum hydride (6.919 g, 182 mmol, 1.5 eq) was suspended in a 5:6 (volume) mixture of diethyl ether:dibutyl ether (220 mL) and cooled to 0°C. N-(2,2-dimethylpropyl)-2,2-dimethylpropanamide (20.701 g, 121 mmol, 1.0 eq) was added to the flask and stirred for 30 minutes. The solution was then refluxed for 42 hours (120°C). The mixture was cooled to room temperature, quenched with deionized water, and filtered. The filtrate was treated with concentrated hydrochloric acid to acidity, and water (400 mL) was added to completely dissolve the solids. The aqueous layer was washed with diethyl ether (3×250 mL), treated with concentrated sodium hydroxide solution to make it alkaline, and extracted with diethyl ether (3×100 mL). The organic layer was dried over sodium sulfate, filtered, and most of the solvent was removed at 40° C. (no vacuum; the amine was volatile). The product was isolated as a light yellow clear ether solution (47.717 g, 36.1 wt %, 91% yield). 1 H-NMR (500MHz, CDCl3) δ2.37(4H,s,N(CH2C(CH3)3)2), 0.94(18H,s,N(CH2C(CH3)3)2). 13 C-NMR (126MHz, CDCl3) δ63.53, 31.96, 27.76. HRMS(EI)C 10 H 23 N[H + ]Calculated value: 158.18; Measured m / z: 158.1908.

[0142] Preparation of N-(2,2-dimethylpropyl)-N,2,2-trimethylpropane-1-amine. An ethereal solution of N-(2,2-dimethylpropyl)-2,2-dimethylpropane-1-amine (16.1 g, (36.1 wt %) in diethyl ether, 112 mmol, 1 eq) was cooled to 0°C and formic acid (11.2 mL, 297 mmol, 2.65 eq) was added dropwise. Formaldehyde [8.50 mL (37 wt % in water), 145 mmol, 1.30 eq] was added and the mixture was refluxed at 60°C for 22 hours. Concentrated hydrochloric acid was added until an acidic pH was reached. The solvent was removed under vacuum at 55°C to give a pink solution. Concentrated sodium hydroxide solution was added until a basic pH was reached. The aqueous layer was extracted with diethyl ether (3 x 150 mL). The organic layer was dried over sodium sulfate, filtered, and most of the solvent was removed at 50°C (no vacuum; the amine is volatile). The product was isolated as a light yellow clear ether solution (27.454 g, 64.1 wt %, 98% yield). Characterization information was found to correspond to literature values ​​(28). 1 H-NMR (300MHz, CDCl3, 20℃) δ2.30(3H,s,NCH3), 2.19(4H,s,N(CH2C(CH3)3)2), 0.88(18H,s,N(CH2C(CH3)3)2). 13 C-NMR (126MHz, CDCl3) δ74.68, 48.25, 33.51, 28.91. HRMS(EI)C 11 H 25 N[H + ]Calculated value: 172.2065; measured m / z: 172.2072.

[0143] Dimethyldineopentylammonium iodide was prepared using a procedure adapted from the literature. A solution of N-(2,2-dimethylpropyl)-N,2,2-trimethylpropane-1-amine in Et2O (64 mass%, 17.07 g, 99.6 mmol, 1 eq.), iodomethane (19 mL, 305 mmol, 3.1 eq.) and acetonitrile (85 mL) were added to a 500 mL round-bottom flask equipped with a stir bar and refluxed for 5 days. The solvent was then removed in vacuo at 45 °C and the product was recrystallized from isopropanol to give 23.826 g of off-white crystals (yield 76%). 1 H-NMR(300MHz,CDCl3)δ3.67(4H,s,N + (CH2C(CH3)3)2),3.47(6H,s,N + (CH3)2),1.25(18H,s,N + (CH2C(CH3)3)2). 13 C-NMR (126MHz, CDCl3) δ77.50, 54.23, 34.07, 30.59. HRMS(EI)C 12 H 28 N[H + ]Calculated value: 186.22; Measured m / z: 186.2222.

[0144] Dimethyldineopentylammonium fluoride was prepared using a procedure adapted from the literature. Silver oxide (24.616 g, 106 mmol, 1.5 eq) was added to a solution of the iodide salt (22.158 g, 70.7 mmol, 1 eq) in deionized water (330 mL) in a 500 mL round bottom flask covered with aluminum foil. After stirring for 1 hour, quantitative ion exchange of iodide with hydroxide was obtained, as confirmed by the absence of precipitation after adding an aliquot to a solution of silver nitrate in concentrated hydrochloric acid. The suspension was filtered and immediately titrated with aqueous hydrofluoric acid (0.5 wt %). HF was added dropwise and the titration was stopped at pH 7.96 (calculated endpoint = 8.08). Most of the water was removed under reduced pressure at 60°C. The solution was further dried by azeotroping with reference grade isopropanol (×3) at 35°C. To remove trace amounts of silver residues, the solution was microfiltered (25 mm wheel filter, 0.45 μm PTFE membrane). The solution was transferred to a sidearm round bottom flask and residual water was removed by azeotroping with dry isopropanol (×5) under high vacuum (~50 mTorr) at 100° C. for 5 days until a light yellow powder remained, according to 19 F NMR, its F - A single peak appears at -75 ppm downfield (in contrast, DF2 - Normalized to -147 ppm). 1 H-NMR(300MHz,CD3CN,20℃)δ3.48(4H,s,N + (CH2C(CH3)3)2),3.34(6H,s,N + (CH3)2),1.19(18H,s,N + (CH2C(CH3)3)2). 13 C-NMR (100MHz, CD3CN) δ77.77, 53.77, 34.06, 30.20. 19 F-NMR(282MHz,CD3CN,20℃)δ-72.87(s,F - ),-147.00(t,DF2 - ). 1 H NMR and 19 F NMR spectra Fig.18A and Fig.18B Shown in.

[0145] Example 3: Electrode Fabrication

[0146] Synthesis of copper nanoparticles: To a stirred solution of hexadecyltrimethylammonium bromide (CTAB) (0.68 g, 1.87 mmol) and citric acid monohydrate (0.08 g, 0.38 mmol) in deionized water (75 mL) at 23 °C under argon was added hydrazine hydrate (50-60%, 3 mL, 17.66 M). The solution was aged under argon for 20 minutes. To a solution of copper (II) nitrate hemihydrate (0.465 g, 2 mmol) and CTAB (0.68 g, 1.87 mmol) in deionized water (75 mL) was added ammonium hydroxide (0.5 mL, 14.5 M). The copper precursor solution was immediately poured into the hydrazine solution and the mixture was stirred under argon for 2 hours. The copper nanoparticles were separated via centrifugation (12,000 rpm, 5 min). The supernatant was discarded and the copper nanoparticles were washed twice with ethanol (10 mL). As Fig.19A The product composition was confirmed by pXRD. The diameter of the copper nanoparticles was ∼50 nm, as shown by Fig.19B as determined by TEM imaging shown in .

[0147] Cu@LaF3 core-shell nanoparticles synthesis: Copper nanoparticles were prepared as described above. After separating the copper nanoparticles by centrifugation (12,000 rpm, 5 min), the supernatant was discarded, and the copper nanoparticles were washed twice with water (30 mL). The Cu nanoparticles were redispersed in deionized water (150 mL) and stirred under argon. Hydrazine hydrate (50-60%, 3 mL, 17.66 M) was added to the Cu nanoparticles and stirred for 10 minutes. A solution of lanthanum nitrate hexahydrate (0.433 g, 1 mmol) in water (15 mL) and a solution of sodium fluoride (0.042 g, 1 mmol) in water (15 mL) were injected into the copper nanoparticle solution simultaneously via a syringe pump (3 mL / min) for 5 minutes. The mixture was then stirred for another 10 minutes under argon. The core-shell material was separated by centrifugation (12,000 rpm, 5 min), the supernatant was discarded, and the remaining core-shell nanoparticles were washed twice with ethanol (10 mL). pXRD showed peaks corresponding to LaF3 and metallic copper, such as Fig.19C The composition of the core-shell product was confirmed by ICP-MS of the powder (Cu:La:F [atomic %] = 77.5:6.8:15.7), EDX microanalysis (Cu:La:F [atomic %] = 94.7:1.6:3.7) and EDS elemental mapping (Cu:La:F [atomic %] = 94.7:1.6:3.7). Fig.19D As determined by the TEM imaging shown in , the copper core has a diameter of 50 nm with a 5 nm thick LaF 3 shell. Fig.19D TEM image of the pristine core-shell nanoparticle shown in FIG. 5 with an inset (lower right inset) showing a high-resolution TEM (HR-TEM) image of a thin LaF 3 shell encapsulating a thicker Cu core.

[0148] Cu-LaF3 thin film preparation: 80nm of copper (Cu sputtering target) was deposited onto a 5×20mm area, 1mm thick glassy carbon (GC) substrate via DC sputtering: 100W; 3mTorr; 63A / min sputtering rate. The Cu-coated substrate was left in the chamber to cool. Then, 80nm of copper (Cu sputtering target) was deposited onto a 5×20mm area, 1mm thick glassy carbon (GC) substrate via RF sputtering: 100W; 3mTorr; 63A / min sputtering rate. 4.5 nm of lanthanum fluoride (LaF3 sputtering target) was deposited on top of the copper film at a sputtering rate of 1.3 Å (angstroms per minute). The coated substrate was then cut into 5×5 mm strips for electrochemical testing. Results from electrochemical testing and XPS are given in Fig. 20A , Fig. 20B , Fig. 20C , Fig.20D and Fig.20E Shown in.

[0149] Film structures similar to the Cu@LaF3 core-shell composite were prepared by sputter deposition onto glassy carbon to give an 80nm Cu core layer covered by a 4.5nm film of LaF3. Cyclic voltammetry was performed as described in the text. Similarly, for the Cu@LaF3 nanoparticle experiments, no Cu or La was detected in the electrolyte after cycling the thin film electrode. Electrochemical cycling in liquid electrolyte followed by a one-hour potential hold (+3.12 V vs. Li + / Li) to drive the system towards the direction of complete conversion of Cu to CuF2 to achieve maximum fluorination of the Cu layer ( Fig. 20A and Fig. 20C ). X-ray photoelectron spectroscopy (XPS) and Ar + Etch / depth measurements were performed to analyze the pristine and fluorinated films. Improved capacity utilization in liquid electrolytes can be achieved by optimizing the relative LaF3 shell thickness and Cu core size. Based on the observed diffusion lengths, Cu@LaF3 nanoparticles with a 2nm shell thickness and a 12nm diameter core can allow for complete conversion of the Cu core to CuF2 on the first charge and much higher material utilization during cycling. Additionally, F can be further improved by using shell materials that are more conductive than LaF3, such as PbSnF4. - Diffusion length. [[PbSnF4 is not claimed]]

[0150] Electrode fabrication: Bismuth, lead, cerium, and calcium foils were cut into thin strips for use in the three-electrode cell. Copper nanoparticles or Cu@LaF3 core-shell nanoparticles were made into a paste with PVDF and / or SP before the three-electrode assembly, pressed into a stainless steel mesh, and dried under vacuum. Cu-LaF3 thin films were prepared as described above and assembled into a three-electrode cell.

[0151] Example 4: Electrochemical testing

[0152] Electrolyte Ionic Conductivity Studies: The ionic conductivity of a number of anhydrous Np1F and Np2F solutions was studied by AC impedance spectroscopy using a VersaSTAT potentiostat. Measurements were made between 100 mHz and 1 MHz using an air-free glass conductivity cell consisting of a Teflon ring sealing the solution between two parallel Pt electrodes. The Pt electrodes were separated by approximately ~1 cm, and the cell constant was determined before each experiment by measuring the conductivity of an aqueous solution of potassium chloride (0.1 M). Thermal control was provided by a Tenney TUJR chamber, allowing the samples to reach thermal equilibrium before measurement (as determined by observing that the impedance spectra did not change with time).

[0153] Electrolyte Voltage Window Determination: Fluoride electrolyte solutions were studied by linear sweep voltammetry using a Bio-Logic VMP2 potentiostat to determine their electrochemical / voltage stability windows using a scan rate of 1 mV / s. These studies employed a Pt working electrode, a Pt auxiliary electrode, and a non-aqueous Ag + / Ag(MeCN) reference electrode and Ar purge. The voltage window was determined by two methods: (i) J 截止 method, which uses 100 μA / cm 2 The limiting current, such as Fig.21A and (ii) a linear fitting method, where the voltage limit is defined as the intersection between the linear fits of the IV curves before and after the onset of electrolyte decomposition, as shown in Fig. 21B , Fig. 21C and Fig.21D The results are shown in Table 1.

[0154] Table 1: Use J 截止 Table of the cathode voltage limit, anode voltage limit and voltage window determined for each electrolyte formulation by the method or linear fit method:

[0155]

[0156] In "stable" solvents such as PN and BTFE ( Fig.24A ), there is no visible HF2 peak next to the observed DF2, indicating that no H / D exchange caused by trace protic solvent impurities occurs on the NMR time scale. Fig.26 In, R 离子 The value represents the diffusion of each ionic species (Np1 + Cation, Np2 + cations or their respective F - The number of BTFE solvent molecules (counter anions) in the electrolytes is shown in Figure 1, and a qualitative picture of the ion solvation sphere in these electrolytes is provided. Rings are drawn around the data points with BTFE structures to illustrate the number of BTFE molecules surrounding and diffusing each ion to roughly depict the solvation sphere. Fig.21A In , the linear sweep voltammogram shows the smoothed data (via polynomial smoothing of the raw data). For the raw data with the fitted results superimposed, see Fig. 21B , 21C and 21D.

[0157] Example 5: Solid Electrolyte Interface (SEI) Formation

[0158] 1H,1H,2H,2H-perfluorooctyltriethoxy-silane (FOTS; 0.25 M) was added to 0.75 M Np1F / BTFE electrolyte. The solution mixture was used in a three-electrode setup with a Ce or Ca working electrode, a Pt wire counter electrode, and a silver wire quasi-reference electrode.

[0159] Table 2: Summary of composition information, electrochemical test parameters, and ICP-MS results for the described example fluoride ion electrochemical cell:

[0160]

[0161]

[0162]

[0163] The grafting of FOTS onto Ce or Ca anodes was achieved by cyclic voltammetry (CV) and monitored in situ via electrochemical impedance spectroscopy (EIS). For CV parameters: a scan rate of 100 mV / s was used, the potential was between -0.8 V and +0.7 V (vs. Li + / Li) for 5 cycles. For EIS parameters: AC impedance spectroscopy measurements were obtained between 0.1Hz and 0.2MHz. A Bio-Logic VMP2 constant potential instrument was used to alternate between CV and EIS electrochemical experiments. The initial experiment was CV, then EIS, then CV, and so on. The experiment alternated from CV to EIS, repeatedly until a total of ten electrochemical experiments had been performed on Ce or Ca anodes. Confirmation of SEI formation on Ce or Ca anodes was obtained via ex situ XPS measurements. An example data set collected using a Ca anode is shown, where the odd-numbered experiments correspond to CV data ( Fig. 10A ) while even-numbered experiments correspond to EIS data ( Fig. 10B ). XPS analysis of a Ca surface grafted with FOTS is also shown as an example ( Fig. 10C ).

[0164] Three-electrode assembly and cycling details: Bismuth, lead, copper, Cu@LaF3, Cu-LaF3 thin film, calcium or cerium electrodes were used as working electrodes in standard three-electrode cells. Platinum wire was used as counter electrode and silver wire in 0.01M AgTOf / MPPy-TFSI was used as non-aqueous pseudo-reference electrode. Specific details about each battery pack, electrolyte composition and cycling parameters used, and ICP-MS data of the electrolyte solution after cycling are listed as shown in Table 2. Electrochemical charge and discharge cycles were performed using a VersaSTAT MC potentiostat.

[0165] Instrumentation: Nuclear magnetic resonance (NMR) spectra were obtained using Mercury Plus 300, Varian 400MR, Inova 500 or Bruker 400 NMR spectrometers. Chemical shifts of protons are given in parts per million downfield from tetramethylsilane as a reference and referenced to residual protons in the NMR solvents: CDCl3 (δ 7.26), CD3CN (δ 1.96). Data are presented as follows: chemical shift, integration, multiplicity (s = singlet, d = doublet, sep = septet, m = multiplet, br = broad), coupling constants in Hertz (Hz) and assignments. Mass spectral data were obtained from the Caltech Mass Spectrometry Facility.

[0166] Pulsed Field Gradient Spin Echo (PFG-SE) 1 H and 19 F NMR experiments were performed on a Varian 500MHz spectrometer with an automatic-xpfg broadband probe, which was connected to a workstation equipped with VnmrJ software (v 4.2). In a glove box filled with Ar, 400 μL of 0.75M Np1F solution (in BTFE or 3:1BTFE:DME) or Np2F solution (in BTFE) was loaded into a 5mm NMR tube, sealed with a rubber septum and fixed with Teflon tape. The NMR tube was removed from the glove box and flame-sealed. The sample was then loaded into the spectrometer and DOSY spectra were recorded (unlocked in a pure proton solvent) at the desired temperature (5-40°C, 5°C increments). The temperature of the probe was calibrated using a methanol standard.

[0167] Inductively coupled plasma mass spectrometry (ICP-MS) was operated by Laboratory Testing, Inc. using a ThermoiCap-Q-Mass Spec. 3 mL of electrolyte was collected after each electrochemical test. The sample was diluted to 10 mL with water to contain 10-30% electrolyte. Prior to ICP-MS analysis, the sample was shaken to thoroughly mix the organic and aqueous layers.

[0168] Powder X-ray diffraction (pXRD) patterns were collected using a Bruker D8ADVANCE instrument with an X-ray generator of 40 kV and 40 mA. The samples after electrochemical testing were loaded into a sealed homemade compartment with a Be window to avoid air and moisture. The parameters of the pXRD scan were in the range of 10 to 90° 2θ, with a step size of 0.027 2θ and a counting time of 12 seconds / step. The pXRD patterns of Cu@LaF3 and Cu precursor powders were collected in air.

[0169] Transmission electron microscopy (TEM) and high-resolution TEM (HR-TEM) images were collected using a FEI Tecnai F20 operating at 200 kV. Energy dispersive spectroscopy (EDS) was performed using an image-corrected FEI Titan3TM G2 60-300 operating at 300 kV equipped with a Super-X four-quadrant detector. The samples after electrochemical testing were dispersed in anhydrous n-hexane (Aldrich) (H2O < 0.5 ppm) in a glove box. 20 μL of the colloidal suspension (1 mg / 1 mL) was drop cast onto a nickel TEM grid with a porous carbon substrate. The samples were vacuum dried for two days and then transferred to the TEM in air. For the as-synthesized copper nanoparticles and Cu@LaF3 nanoparticles, the TEM samples were dispersed in ethanol and drop cast on a nickel grid.

[0170] XPS depth profiling analysis was performed by Nanolab Technologies using a K-Alpha manufactured by Thermo Fisher Scientific, Inc. TM + X-ray photoelectron spectroscopy (XPS) system. The sample was not exposed to X-rays until the start of the measurement to minimize the possibility of degradation. The X-rays were monochromatic Al K α 1486eV The etch rate of thermally grown SiO2 was used as a rough measure of etch depth. The size of the argon ion etch pit was 4 x 2 mm and the size of the X-ray beam was 0.4 mm. + Etching for SiO2 The depth analysis was performed with an Ar at 0.5 kV. + beam voltage, 30 degree incident angle and for SiO2 The etching rate is obtained.

[0171] STEM images and EELS spectra were obtained using a Jeol2100F microscope equipped with a GIF Tridiem Gatan EELS spectrometer. EELS spectra were recorded at 120 kV, and EELS point spectra were acquired at an accelerating voltage of 200 kV. The probe size for mapping was 1.5 nm, and the probe size for point collection was 0.7 nm. The incident and exit angles of the electron beam were 12 mrad. The energy resolution was 1.0 eV as measured by the full width at half maximum of the zero-loss peak in vacuum. All EELS spectra were obtained between 390 eV and 1000 eV, with an energy step of 0.3 eV and an exposure time of 1 second. Elemental analysis was performed by using the standard Gatan / EELS software assuming that the background before the absorption edge conforms to a power law and the Hartree-Slater model for quantification. In order to analyze La M 5,4 For absorption edge spectra, we first remove the background before the absorption edge and then subtract two values ​​of the same amplitude from the data in the form of 1 / (1+e -x ) - minus one at each of the M5 and M4 absorption edges as an absorption edge jump. The least squares fit of the M5 and M4 peaks was performed by constraining the amplitude, loss energy and FWHM. The M5 / M4 ratio was calculated using the exact amplitude. The sample was transferred to a nitrogen glove bag and dispersed in anhydrous n-hexane (Aldrich). 20 μL of the colloidal suspension (1 mg / 1 mL) was drop cast onto a Ni TEM grid with a porous carbon substrate. The sample was vacuum dried for 2 days before TEM analysis. The sample was transferred to a TEM holder in air.

[0172] Computational methods and calculations: All molecular dynamics simulations were performed using LAMMPS (Large Atomic / Molecular Massively Parallel Simulator). All simulations used a one fs integration time step, Velocity-Verlet integration, and periodic boundary conditions. The particle-particle-particle-mesh (PPPM) algorithm was used to model long-range electrostatic interactions and the Lennard-Jones interaction was All simulations were initialized from a diffuse configuration containing at least 1500 atoms, using a cubic grid to place solvent molecules in random orientations without overlap. The simulations were first relaxed in the NVE ensemble, with atomic displacements constrained to 1000 atoms per time step. The simulations were then equilibrated for 30 ps, ​​followed by 1 ns of NPT equilibration, where the temperature was linearly increased from 100 K to 298 K to simplify the simulations. The simulations were further equilibrated for 2 ns at 298 K in the NPT ensemble before ion insertion for solvation free energy calculations. In the NPT simulations, a Nosé-Hoover thermostat and barostat were employed, using a modification of that proposed by Martyna, Tobias, and Klein as implemented in LAMMPS. For the reported radial distribution functions (RDFs), individual ions were randomly inserted into the pre-equilibrated solvent simulation system, allowed to equilibrate for a further 1 ns in the NPT ensemble, and then RDFs were generated from another 10 ns of production data. The F was calculated. - The radial distribution function ( Fig. 22 ) to characterize the strength of its interaction with the α-CX2 (X = H or F) portion of the indicated solvent. For BTFE, the distance from the H atom of the α-CH2 group is about (Angstroms), F - The probability of interaction is large; for diethylene glycol dimethyl ether, the corresponding probability is greatly reduced. BPFE shows very small F at all partitions - Possibility of interaction with F-containing backbones.

[0173] Since several of the solvents proposed in this study are novel, no suitable force fields are available. Therefore, all solvent force fields in this study were used on the basis of density functional theory (DFT) quantum chemical calculations. The solvent force field was parameterized using the B3LYP-D3 / def2-TZVP level of theory calculated using the software package. The solvent force field was parameterized using the OPLS force field function form as described previously, except that 1-4 pairwise interactions were excluded from the non-bonded interaction calculations. In brief, the bond, angle, and dihedral force field terms were derived from the potential energy curves calculated for the internal degrees of freedom of each molecule in vacuum, thereby optimizing the other degrees of freedom as a function of the pattern scan. The resulting energy curves were self-consistently fitted to obtain the corresponding force constant parameters and equilibrium displacement parameters in the force field. The Lennard-Jones parameters were obtained from the Universal Force Field (UFF), and the partial charges of all molecules and ions were calculated from CHELPG (which uses a grid-based method to fit electrostatic potential charges), which were calculated based on the best geometry of each molecule.

[0174] Quantum chemical calculations were used to characterize the partial charge distribution in BTFE and diethylene glycol dimethyl ether ( Fig.23A ). - BTFE in the solvated structure exhibits a larger partial positive charge (0.12) on the hydrogen atoms of the α-CH2 moiety than diethylene glycol dimethyl ether (0.01) because BTFE has two electron withdrawing groups on the side of the α-CH2 moiety. Fig. 23B The F in liquid BTFE is shown in - The innermost solvation shell of BTFE. + The solvation shell of the cation is more complex, but qualitatively, the β-CF3 group on BTFE is + The solvated structures seem to be most common ( Fig.23C ).

[0175] Thermodynamic integration was used to calculate the ion-specific solvation free energy in each solvent. The Lennard-Jones (U LJ ) and Coulomb (U C ) potential to gradually introduce ion-solvent potential energy terms

[0176] U LJ (λ LJ )=U S +λ LJ U LJ Formula S1

[0177] where λ LJ is the solvent-ion Lennard-Jones interaction (U LJ ) and

[0178] U C (λ C )=U S+LJ +λ C U C Formula S2

[0179] where λ C is the linear scaling parameter for the solvent-ion Coulomb interaction. The potential in Eq. S1 is calculated using the standard λ-dependent soft-core Lennard-Jones potential, as implemented in LAMMPS, with n = 1 and α LJ = 0.5. The potential in equation S2 is obtained by multiplying the charge on the ion by the ratio λ C The total solvation free energy is obtained by

[0180]

[0181] The brackets in Eq. S3 indicate the ensemble average, and an approximation has been made that the contribution of PΔV to the free energy change can be safely ignored. The integral in Eq. S3 is solved numerically using the trapezoidal rule, where λ LJ and λ C The steps were incremented in steps of 0.2 (twenty-one steps in total, eleven for the Lennard-Jones phase and eleven for electrostatic interactions, with less than one redundant step connecting the two phases). The system was allowed to equilibrate for 250 ps at each λ-step and then the dynamics for another 250 ps were used to calculate the necessary derivatives. The derivatives in Eq. S3 were calculated by finite differences. At the endpoints, forward or backward finite differences were used, and at all other points, central differences (λ-step size of 0.01) were used to solve the derivatives. In the case of polyatomic cations, an additional free energy contribution associated with the removal of intramolecular electrostatic interactions must be calculated. Free energy perturbations were used to evaluate this contribution for 10 ns MD trajectories of individual cations in vacuum. The reported ΔG TI The values ​​were calculated as the mean of all ion insertion trajectories, and the error of the mean was estimated by bootstrap resampling (5 million samples).

[0182] The pKa values ​​of acetonitrile, propionitrile and BTFE were calculated according to the following formula:

[0183]

[0184] where ΔG -H,i is the free energy of deprotonation of species i, R is the ideal gas constant, T is 298 K, and a and b are the calibration constants (39-41) obtained by least squares fitting of Equation S4 for the experimental pKa values ​​of reference solvents (1,2,3,4,5-pentamethylcyclopenta-1,3-diene, pKa = 26.1; cyclopenta-1,3-diene, pKa = 18.0; dimethyl 2-(trifluoromethyl)malonate, pKa = 10.8; dimethyl 2-methylmalonate, pKa = 18.0; dimethyl malonate, pKa = 15.9; 1,1,1,3,3,3-hexafluoro-2-(trifluoromethyl)propane, pKa = 11.0; methane, pKa = 56.0; and acetonitrile, pKa = 31.3). ΔG -H,i The calculations were performed by first geometry optimizing the neutral and deprotonated species in vacuum, followed by additional geometry optimization using the COSMO polarized continuum model and a dielectric constant of 46.7 to match the DMSO reference solvent. After geometry optimization, frequency calculations were performed to obtain a zero-point energy correction for the free energy. The difference in single-point energies after the zero-point energy correction yielded the ΔG for each species. -H,i All quantum chemical calculations were performed at the B3LYP-D3 / ma-def2-TZVP level of theory. The calculated solvent pKa of acetonitrile is 31, while the reported value in the literature is 31.3. The calculated solvent pKa of propionitrile is 33; for comparison, the reported value in the literature is 32.5. The calculated pKa of BTFE is 35.

[0185] Solvent screening and F using Np1F - Long-term stability of ions in non-aqueous solutions

[0186] All solvent screening experiments in this study were performed in an argon-filled glove box (H2O ≤ 10 ppm). Solvents were purchased commercially and used The molecular sieves were dried until anhydrous, as measured by Karl Fisher titration. Prior to solvent screening, the purity of all solvents so treated was confirmed by NMR spectroscopy. Solvent screening was performed by dissolving anhydrous Np1F in anhydrous solvent until the solution was saturated. An analytical balance was used in a glove box to record the weight (grams) of 5 mL of oven-dried scintillation vials, solvent, and Np1F, so that the saturation concentration (M) of Np1F in the solvent could be subsequently determined. An aliquot of the saturated solution was then transferred into an oven-dried NMR tube containing 0.5 mL of CD3CN NMR solvent, sealed, and then removed from the glove box for analysis. 1 H and 19 F NMR spectral analysis. Two reactions: (i) CH3CN and F - HF2 - and (ii) CD3CN and F - DF2 - The characterization of is well established in the literature (43). All screened solvents are expected to 19 F NMR showed that the - The triplet peak of HF2 (δ = -147.0 ppm; J = 18 Hz) is - and DF2 - There is no rapid exchange between them (17,43), so 1 H NMR showed that the - A new triplet peak (δ = 16 ppm; J = 121 Hz) and / or 19 F NMR showed that the - The doublet peak (δ = -146.6 ppm; J = 121 Hz) of - Indication of reaction with the screened solvent.

[0187] Initial screening of Np1F revealed three broad classes of organic solvents (as described in the main text). Examples of class (b) solvents include nitriles such as acetonitrile (ACN), 2-methoxyacetonitrile, 3-methoxypropionitrile (MeOPN), and pyridines such as 2,6-difluoropyridine, while examples of class (c) solvents include propionitrile (PN), 3-fluorobenzonitrile, and 1-methyl-1-propylpyrrolidinium bis(trifluorosulfonyl)imide (MPPy-TFSI).

[0188] In determining PN and BTFE is F - After the excellent solvent for the stable solvation of ions was prepared, two J.Young NMR tubes containing anhydrous Np1F / PN and Np1F / BTFE solutions (both without CD3CN NMR solvents) were prepared and sealed in an inert atmosphere. These J.Young tubes were stored on the bench at room temperature for more than 140 days. 1 H and 19 F NMR monitoring of F - Long-term stability of ions ( Fig.24A To our surprise, the initial NMR spectra of both Np1F / PN and Np1F / BTFE showed slight traces of HF2 - The initial F - Relative to trace amounts of HF2 - Normalized to 100%. Over time, %HF2 - Increase, accompanied by %F - A slight but observable decrease.

[0189] Although F - The reaction between F and CH3CN is known, but it is still necessary to explore - Is it a strong enough base to deprotonate PN or BTFE? The pKa of acetonitrile, PN and BTFE were calculated using the calculation method described above. Fig. 24B and Fig.24C As shown in Figure 2, HF2 was never observed in these solutions when CD3CN NMR solvents were used. - Although F - The reaction with CD3CN is well characterized, but similar behavior with PN and BTFE has not been described in the literature. - To determine whether it is due to the reactivity with PN or BTFE, a set of control NMR experiments were performed using deuterated PN (d5-PN) and CD3CN ( Fig.24D ). In the CD3CN solution, DF2 was observed as expected. - This is because the acidic CD3 group is - Deprotonation caused by HF2 - . F - The reaction with CD3CN must therefore prevail over the reaction with any trace protic impurities (due to the large excess of CD3CN). For the d5-PN solution, the opposite behavior was observed: F - Does not react with d5-PN solvent to produce DF2 - , but reacts with an unidentified proton impurity (present in trace amounts) to form a small amount of HF2 - . In view of this, we conclude that under these conditions, F - Not a strong enough base to strip deuterium from d5-PN.

[0190] Deuterated BTFE is not commercially available, and our attempts to synthesize d4-BTFE ourselves were unsuccessful. The pKa of acetonitrile, PN, and BTFE were calculated using the calculation method described above. The calculated values ​​for acetonitrile and PN are in good agreement with the literature (the calculated solvent pKa of acetonitrile is 31, while the value reported in the literature is 31.3; the calculated solvent pKa of propionitrile is 33, while the value reported in the literature is 32.5; the calculated pKa of BTFE is 35).

[0191] Comparing the calculated pKa values ​​of acetonitrile, PN, and BTFE, BTFE appears to be significantly less acidic than PN and, therefore, is a promising candidate for use as a catalyst for F. - Therefore, we conclude that the trace amounts of HF2 observed in Np1F / PN, Np1F / d5-PN, and Np1F / BTFE solutions (in the absence of CD3CN) - The proton concentration of F is due to the presence of a small amount of unknown proton impurities in the system, rather than being derived from the deprotonation of the bulk solvent. In general, when stored in an anhydrous, non-aqueous liquid solution (e.g., PN or BTFE) at room temperature under an inert atmosphere, F - Ions are chemically stable for long periods of time.

[0192] Solution Properties of Ion Movement in Fluoride Ion Electrolytes

[0193] To fully characterize the ionic properties in liquid solutions, pulsed field gradient spin echo (PFG-SE) was performed on three electrolyte preparations. 1 H and 19 F NMR and AC impedance measurements (Tables 3, 4 and 5 below). Self-diffusion coefficient (D Np+ +D F- ) reveals that the activation energy of Np1F / BTFE electrolyte is higher than that of Np2F / BTFE electrolyte ( Fig.25A ), while the ion conduction activation energies of the two electrolytes are comparable ( Fig.25B ). Calculate Np using Equation S5 + Cation (t + ) and F - Anion (t - )

[0194]

[0195] Where D n is the self-diffusion coefficient of the indicated ion (in m 2 / s), such as by pulsed field gradient spin echo (PFG-SE) 1 H and 19 Measured by F NMR.

[0196] The ion dissociation degree (α) was calculated using Equation S6 (45):

[0197]

[0198] where σ ac is the ionic conductivity determined by AC impedance (unit: S / m) and σ nmr is the ionic conductivity (unit: S / m) determined by PFG-SE NMR via the Nernst-Einstein equation (Equation S7).

[0199]

[0200] The Nernst-Einstein equation relates the ionic diffusion coefficient to the ionic conductivity, where N is the mass per m 3 The number of ions, e is the elementary charge (unit C), k B is the Boltzmann constant, and T is the temperature (in K). When the degree of ion dissociation is very small (α<<1), the migration number of both anions and cations will be about 0.5, indicating a high degree of ion pairing in the electrolyte. The ion pairing can be corrected using an ion pair correction factor (ξ), which can be determined using Equation S8.

[0201] ξ=2D Np + (α-0.5)+D F- Formula S8

[0202] The migration number calculated using Equation S5 assumes that no ion pairing occurs. The migration number that results in ion pairing can be calculated using the modified equation (Equation S9):

[0203]

[0204] The anion (R F ) or cation (R Np )’s Stokes radius (Equation S10).

[0205]

[0206] The R value is rounded to the nearest integer and indicates how many solvent molecules diffuse together per anion (or cation) on average. This provides a rough picture of the solvation sphere surrounding a given ion. + Cations and F - The anions have the same NMR-determined Stokes radius (R 离子 )value( Fig.26 ), therefore, the two ions diffuse together with two BTFE solvent molecules as a tight ion pair, qualitatively represented as "BTFE-Np1 + -F - -BTFE". In Np2F / BTFE electrolyte, Np2 + and F - The Stokes radius is different (R Np2 =3, R F =2), indicating that despite the presence of ion pairing, the solvation environment is unique and the situation is close to that of "(BTFE)2-Np2 + -BTFE-F - -BTFE". Therefore, the increase in ion separation and Np2 + Higher solvation of the cation is the factor that affects F - The lower energy barrier for mobility and leads to an auxiliary factor for the improved conductivity of the Np2F / BTFE electrolyte. The results from the PFG-SENMR and AC impedance measurements of the three fluoride electrolyte formulations are listed in Tables 3, 4 and 5 below.

[0207] Table 3: AC impedance ionic conductivity and PFG-SE NMR diffusion measurements of 0.75M Np1F in BTFE.

[0208]

[0209] a Error from the VnmrJ program. b D BTFE Represents the mean ± SD of four diffusion coefficients determined for each of the quartet corresponding to the methylene protons of the BTFE solvent. c The error is ±0.0002 S / m (standard deviation of five measurements). d The error is ±0.001.

[0210] Table 4: AC impedance ionic conductivity and PFG-SE NMR diffusion measurements of 0.75M Np2F in BTFE.

[0211]

[0212] a Error from the VnmrJ program. b D BTFE Represents the mean ± SD of four diffusion coefficients determined for each of the quartet corresponding to the methylene protons of the BTFE solvent. c The error is ±0.0002 S / m (standard deviation of five measurements). d The error is ±0.001.

[0213] Table 5: AC impedance ionic conductivity and PFG-SE NMR diffusion measurements of 0.75M Np1F in BTFE:DME (3:1).

[0214]

[0215] a Error from the VnmrJ program. b D BTFE Represents the mean ± SD of four diffusion coefficients determined for each of the quartet corresponding to the methylene protons of the BTFE solvent. c The error is ±0.0002 S / m (standard deviation of five measurements). d The error is ±0.0006.

[0216] Interfacial properties of fluoride electrolytes at the surface of metal electrodes

[0217] In order to determine the liquid F - To investigate whether the electrolyte is electrochemically active to promote the conversion reactions at the metal electrode surface, we performed half-cell experiments on a variety of metal electrode materials. BiF3, PbF2, and CuF2 cathodes have high theoretical specific capacities (302 mAh / g, 360 mAh / g, and 528 mAh / g, respectively) and have demonstrated limited cycling in high-temperature FIBs by direct multivalent conversions, thus avoiding any lower oxidation state intermediate phases such as CuF. We achieved electrochemical cycling of Bi, Pb, and Cu electrodes in a three-electrode cell at room temperature in our liquid electrolyte, demonstrating up to 10 cycles ( Figures 27A-27E Powder X-ray diffraction (pXRD) showed that upon electrochemical fluorination, Bi was converted to BiF3 and Pb was converted to β-PbF2, while the Cu electrode appeared unchanged over the entire cycling process ( Figures 28A-28B ). In all cases, performance was less than ideal: after discharge, the BiF3 peaks were still present in the pXRD pattern, indicating that the conversion reaction was not fully reversible under these conditions. The fluorination and defluorination of Pb appeared to be fully reversible, however, ICP-MS revealed that 3.9% of the Pb had dissolved into the liquid electrolyte after ~7 hours of cycling (similar values ​​were measured for Bi). Similarly, although electrochemical conversion of Cu to CuF2 has been demonstrated to occur in solid-state devices, a high degree of Cu dissolution (4.0 atomic %) was found to occur in the liquid electrolyte. Thus, although electrochemical oxidation of Cu was presumed to occur, the Cu 2+ The dissolution of CuF2 is faster than the formation of CuF2 and / or after formation the CuF2 will be rapidly filtered into the electrolyte.

[0218] This liquid F - The electrolyte is also electrochemically active in promoting conversion reactions at the more electropositive metal surface. Half-cell cycling experiments with Ce showed successful fluorination to form CeF3 after the first charge (Figure 9). However, after the first discharge, CeF3 was only partially defluorinated, indicating that the conversion reaction was not fully reversible under these conditions and electrolyte decomposition may be significant. Such electrolyte decomposition is a common phenomenon that occurs in the first few cycles of battery operation, such as in lithium-ion batteries, which leads to the formation of a passive solid electrolyte interface (SEI) layer on the anode surface, which can be "tailored" to block further electrolyte degradation and electron transport while maintaining favorable ion diffusion properties. Therefore, we reasoned that SEI-promoting additives with the necessary chemical properties (i.e., sacrificially reduced, surface-reactive perfluoroalkyl ligands) may improve the cycling properties of electropositive metals and identified 1H,1H,2H,2H-perfluorooctyltriethoxysilane (FOTS) as a suitable material. Pretreatment of Ca or Ce anodes was performed by cyclic voltammetry in 0.75 M Np1F / BTFE electrolyte containing 0.25 M FOTS additive ( Figures 10A-10C The desired CF-containing surface was achieved, as confirmed by in situ monitoring by electrochemical impedance spectroscopy (EIS) and using ex situ XPS analysis. n The formation of SEI layer ( Figures 10A-10C It is worth noting that the use of Ce metal pretreated with a FOTS-derived SEI layer can significantly improve the reversibility of the Ce to CeF3 conversion reaction ( Fig.11A and Fig. 11B However, no cycling of Ca was observed under any of the conditions studied; this may indicate that, compared to the more compact fluorite CaF2 (note, Ca 2+ and Ce 3+ The conversion of the higher coordinated CeF3 fluorocerite structure is kinetically much more favorable. However, from an energy density perspective, the increased mass of Ce (or other lanthanide metals) compared to Ca is offset by the higher density and three-electron activity of the former (574 mAh / g; 3845 mAh / cm, respectively). 3 Compare 1337mAh / g; 2073mAh / cm 3 ).

[0219] LaF3 is only found in the shell region, while CuF2 is evident in the interface region ( Fig.29A , left inset). Metallic Cu is found in the core 0 , and partially or fully fluorinated Cu states were detected at the interface region ( Fig.29A , right inset). The average elemental composition extracted from the EELS spectrum shows that the core contains only Cu, the interface contains Cu and F, and the shell contains La and F ( Fig.29B ). More fluorine was found in the interface region (30 ± 20 atom %) than in the outer shell (14 ± 12 atom %), indicating that LaF3 does allow F - As expected, La is significantly more abundant in the outer shell (9 ± 8 atom %) than at the interface (1.1 ± 1.3 atom %), suggesting that the shell is robust and does not interfere with chemical reactions occurring at the interface or at the core. 5,4 and Cu L 3,2 Comparison of 3D-surface maps of the absorption edges shows that the core-shell nanoparticles maintain their size, morphology, and composition before and after electrochemical cycling. It should be noted that electron beam damage prevents detailed EELS analysis of the defluorinated nanoparticles. This may be due to the residual solvent promoting the softening of the nanoparticles as they transition from a crystalline to an amorphous state, while soft matter is more susceptible to electron beam damage.

[0220] Example 6: All-atom molecular dynamics simulation of self-assembled monolayer interface for metal electrode passivation

[0221] All-atom molecular dynamics simulations were performed to explore the design rules for self-assembled monolayers (SAMs) of metal electrodes in passivated fluoride ion batteries. Four different SEM molecules were investigated with respect to the presence of αCH2 and / or fluorinated carbon (CF2) moieties, including E-(CH2)2(CH2OCH2CF2)2F, E-(CH2)2(CF2CH2)3CF3, E-(CH2)2(CH2OCH2)3H, and E-(CH2)2(CF2)7CF3. Here, E stands for electrode. Both considerations are related to fluoride ion solvation. The fluoride salt Np2F (N,N-dimethyl-N,N-dineopentylammonium fluoride) was introduced at a molar density of approximately 1.2 M into simulated cells employing either BTFE (bis(2,2,2-trifluoroethyl) ether) or ethylene glycol dimethyl ether electrolytes. Based on simulation results (which take into account both the statistics and kinetics of fluoride ion SAM intercalation discussed below), the combination of (CH2OCH2CF2)2F and ethylene glycol dimethyl ether was found to be the best among the set of investigated combinations between SAM moieties and solvents.

[0222] The model metal electrodes were maintained at a constant potential (V), each maintained at V = V - or V + The bias potential is ΔV = V + -V - The charge of the metal atoms fluctuates over time. By doing so, the charge polarization of the electrodes and image-charge effects are included in the simulation.

[0223] The SAM coverage density (5.625nm -2 ) is high enough to prevent the electrolyte from embedding into the SAM region, thus meeting the main requirement for electrode passivation. At this SAM coverage density, most of the SAM molecules stand up relative to the electrode. Thereafter, the SAM region is 1.5 m from each electrode.

[0224] Fig.30 The simulation results of the fluoride ion SAM embedding statistics at ΔV = 0 (zero bias potential) are given. Compared with the SAM of (CH2OCH2)3H molecules, the SAMs of CH2OCH2CF2 and CF2CH2 parts show a higher average local density of fluoride ions in the SAM region. <c>(0.3-0.5M) and shorter average distance between fluoride ions and electrodes <d> The SAM area considered is the distance from each electrode This seems to be the case whether the electrolyte is BTFE or ethylene glycol dimethyl ether. The SAM of (CF2)7CF3 molecules does not allow the fluoride ion SAM to intercalate. This observation suggests that it is necessary for both the CF2 and CH2 moieties to be adjacent to each other for the SAM to not hinder convenient fluoride ion SAM intercalation.

[0225] Hereinafter, a discussion is given only for SAMs of CH2OCH2CF2 and CF2CH2 moieties, which allow for significant fluoride ion SAM intercalation.

[0226] See also Fig.31A , which presents the calculated mean force potential (PMF) of the SAM of CH2OCH2CF2 and CF2CH2 moieties at several electrode potentials (V = -1, 0, +1 V) in the case of BTFE or ethylene glycol dimethyl ether electrolyte. Electrode polarization will change the PMF, thereby enhancing or retarding the insertion of fluoride ion SAM. There is a potential barrier of about 2 / β, where β -1 =k B T, k B is the Boltzmann constant and T = 400 K. This barrier separates the SAM from the electrolyte region, which is related to the fluoride ion SAM intercalation kinetics. This observation suggests that intercalation kinetics may play an important role in SAM design.

[0227] See also Fig.31B -C, which presents the calculated average local density of fluoride ions in the SAM region of the CH2OCH2CF2 and CF2CH2 moieties at several electrode potentials (V = -1, 0, +1 V) in the case of BTFE or ethylene glycol dimethyl ether electrolytes <c>and shorter average distance between fluoride ions and the electrode <d>Compared with the SAM of (CF2CH2)3CF3 molecules, the SAM of the CH2OCH2CF2 part not only allows more fluoride ions to be embedded but also is closer to the electrode, i.e., higher <c>and smaller <d>This appears to be the case at all electrode potentials investigated, whether the electrolyte is BTFE or ethylene glycol dimethyl ether. Therefore, based on the fluoride ion SAM intercalation statistics, the SAM of the CH2OCH2CF2 moiety is considered to be the best among those considered here.

[0228] Fig.32A Schematic diagram of the solvation of fluoride ions in SAM. Orange solid lines are drawn between the fluoride ions within . These hydrogen atoms are considered to be "accompanied" by the solvation of the fluoride ions.

[0229] See also Fig.32B , which presents the solvation and kinetics of fluoride ions in SAMs of CH2OCH2CF2 and CF2CH2 moieties at ΔV = 0 in the presence of BTFE or ethylene glycol dimethyl ether electrolytes. It is confirmed that the CH2 moiety of the SAM is responsible for the solvation of fluoride ions, which is adjacent to the CF2 moiety.

[0230] See also Fig.32C , which presents the calculated rate of "companion" hydrogen exchange for the bond between the fluoride ion and its companion hydrogen atom of the SAM molecule using the time-dependent function H(t) When H(t) decays from 1 to 0, τ ex Use H(τ ex )=e -1 Definition. "Chaperone" exchange is a process that occurs in ~1 ns and is associated with the hopping motion of fluoride ions within the SAM region.

[0231] See also Fig.33 , using the time correlation function F AB (t) Calculated rate of fluoride ion deintercalation at several electrode potentials When fluoride ions are deintercalated from the SAM region to the electrolyte region, F AB (t) decays from 1 to 0. τ de Using F AB (τ de )=e -1 Definition. Compared with the chaperone exchange process, deintercalation is a much slower process (>20ns), which is attributed to Fig.31A The PMF shown in Figure 1 presents a considerable barrier for the fluoride ions to overcome.

[0232] Electrode polarization will affect the deintercalation kinetics, either enhancing or retarding the deintercalation process. Furthermore, the deintercalation kinetics depend on the electrolyte: the deintercalation from the SAM of CH2OCH2CF2 is faster than that from the SAM of the CF2CH2 moiety in the case of the glycol dimethyl ether electrolyte, but slower in the case of the BTFE electrolyte. This seems to be the case at all electrode potentials investigated. Using finite electrode potentials, the SAM of CH2OCH2CF2 allows the most convenient deintercalation of fluoride ions in the case of the glycol dimethyl ether electrolyte.

[0233] Simulation results of the statistics and kinetics of fluoride SAM intercalation suggest the following design rules for functional passivating SAMs: (i) formation ability; sufficiently dense SAM surface coverage to prevent electrolyte solvent intercalation; (ii) the need for both α-CH2 and CF2 moieties for fluoride solvation, or the need for other moieties to interact favorably with fluoride to ensure a large amount of fluoride SAM intercalation; (iii) compatibility with the electrolyte to ensure sufficient kinetics for fluoride SAM intercalation and deintercalation, and (iv) suitable end groups facing the electrolyte to reduce the barrier for fluoride SAM intercalation to ensure sufficient kinetics for fluoride SAM intercalation and deintercalation.

[0234] A schematic representation of the fluoride ion solvation sites can be obtained from these MD calculations ( Fig.34 ).exist Fig.34 In the figure, dark gray indicates electrode atoms, gray indicates carbon atoms, red indicates oxygen atoms, white indicates hydrogen atoms, pink indicates fluorine atoms, and green indicates solvation sites. The figure presents a snapshot of the spatial position where fluoride ions can be favorably solvated or bound within the SAM. According to other work on lithium ion solvation, including Webb et al., "Systematic computational and experimental investigation of lithium-ion transport mechanisms in polyester-based polymer electrolytes." ACS Cent. Sci., 1, 198 (2015); Webb et al., "Chemically specific dynamic bond percolation model for ion transport in polymerelectrolytes." Macromolecules, 48, 7346 (2015); and Miller et al., "Designing polymerelectrolytes for safe and high capacity rechargeable lithium batteries." Acc. Chem. Res., 50, 590 (2017), all of which are incorporated herein by reference in their entirety, the fluoride ion solvation site distribution is determined using a distance-based criterion under each SAM configuration. The solvation sites are "trimmed" to avoid excess and steric clashes with other atoms in the SAM.

[0235] The scheme used is:

[0236] 1. First, prepare sites on a rectangular grid (146520 sites).

[0237] 2. If they have at least 4 hydrogen atoms near the SAM molecule ( If the number of sites is within 100, these sites are collected.

[0238] 3. Two sites are considered identical if they share at least the same 4 nearest hydrogens. The position of a representative site of a group of sites with the same 4 nearest hydrogens is the centroid of these sites.

[0239] 3. The site should not have significant overlap with all other atoms of the SAM molecule and the electrode (interatomic distance ).

[0240] 4. If a) they share at least 2 hydrogen atoms in common, and b) their inter-site distance is less than The last step is to merge the sites. The position of the final merged site is the centroid of the merged sites.< / d> < / c> < / d> < / c> < / d> < / c> < / d> < / c> < / d> < / c>

Claims

1. A fluoride ion battery comprising: a liquid electrolyte comprising fluoride ions; an anode comprising an alkaline earth metal, a rare earth metal, or a combination thereof and having an outer solid electrolyte interphase layer in contact with the electrolyte; and A cathode, the cathode comprising: A core-shell particle having a transition metal core and a shell at least partially surrounding the transition metal core, the shell being in contact with the electrolyte, or A metallic nanostructure core and a shell, the metallic nanostructure core comprising at least one dimension less than or equal to 20 nm, the shell at least partially surrounding the core.

2. The fluoride ion battery of claim 1, wherein the liquid electrolyte comprises bis(2-methoxyethyl) ether, bis(2,2,2-trifluoroethyl) ether, N,N,N-trimethyl-N-neopentylammonium fluoride, N,N-dimethyl-N,N-dineopentylammonium fluoride, propionitrile, or a combination thereof.

3. The fluoride ion battery of claim 1, wherein the alkaline earth metal is calcium and the rare earth metal is selected from cerium and lanthanum.

4. The fluoride ion battery of claim 1, wherein the transition metal core comprises bismuth, lead, copper, or a combination thereof.

5. The fluoride ion battery of claim 1 , wherein the outer solid electrolyte interphase layer is covalently bonded to the anode, the outer solid electrolyte interphase layer comprising CF3(CF2)5CH2, CF3(CF2)2CH2, p-tert-butylphenyl, p-methoxyphenyl, p-(dimethylamino)phenyl, p-nitrophenyl, p-trifluoromethylphenyl, or a combination thereof.

6. The fluoride ion battery of claim 1 , wherein the outer solid electrolyte interphase layer comprises 1H,1H,2H,2H-perfluorooctyltriethoxysilane, 3,3,4,4,5,5,6,6,6-nonafluorohex-1-ene, 4-tert-butylbenzene diazonium salt, 4-methoxybenzene diazonium salt, 4-(dimethylamino)benzene diazonium salt, 4-nitrobenzene diazonium salt, 4-trifluoromethylbenzene diazonium salt, or a combination thereof.

7. The fluoride ion battery of claim 6, wherein the outer solid electrolyte interphase layer is a film on the anode, and the 4-tert-butylbenzene diazonium salt, 4-methoxybenzene diazonium salt, 4-(dimethylamino)benzene diazonium salt, 4-nitrobenzene diazonium salt, 4-trifluoromethylbenzene diazonium salt, or a combination thereof comprises a counter anion of a salt, the counter anion comprising BF4 - 、F - , Cl - PF6 - CF3SO3 - 、[(CF3SO2)2N] - or a combination thereof.

8. The fluoride ion battery of claim 1, wherein the transition metal core comprises copper and the shell comprises LaF3.

9. The fluoride ion battery of claim 1, wherein the shell has a thickness of 2 nm to 5 nm.

10. The fluoride ion battery of claim 1, wherein the transition metal core has at least one dimension less than or equal to 20 nm.

11. A method of making a fluoride ion battery, the method comprising: providing a liquid electrolyte, the liquid electrolyte comprising an additive; Providing a working electrode in contact with the electrolyte, the working electrode comprising an alkaline earth metal, a rare earth metal, or a combination thereof; providing a counter electrode in contact with the electrolyte; The voltage potential between the working electrode and the counter electrode is varied between a first potential and a second potential for several cycles until the additive forms an outer solid electrolyte phase interface layer on the working electrode, the second potential being higher than the first potential.

12. The method of claim 11, wherein the liquid electrolyte comprises bis(2-methoxyethyl)ether, bis(2,2,2-trifluoroethyl)ether, N,N,N-trimethyl-N-neopentylammonium fluoride, propionitrile, N,N-dimethyl-N,N-dineopentylammonium fluoride, or a combination thereof.

13. The method according to claim 11, wherein relative to Li + / Li, the first potential is -0.8V and the second potential is +0.7V, the number of cycles is at most five times, and the additive comprises 1H,1H,2H,2H-perfluorooctyltriethoxysilane, 3,3,4,4,5,5,6,6,6-nonafluorohex-1-ene or a combination thereof.

14. The method according to claim 11, wherein relative to Li + / Li, the first potential is -1.0V and the second potential is +0.8V, the number of cycles is at most 20 times, and the additive is selected from 4-tert-butylbenzene diazonium salt, 4-methoxybenzene diazonium salt, 4-(dimethylamino)benzene diazonium salt, 4-nitrobenzene diazonium salt, 4-trifluoromethylbenzene diazonium salt, their variations or combinations thereof.

15. The method of claim 11, wherein the working electrode comprises calcium, cerium, lanthanum, or a combination thereof.

16. A method of making a cathode for a fluoride ion battery according to any one of claims 1 to 10, the method comprising: Providing a solid transition metal; The solid transition metal is treated with lanthanum and fluorine to form a LaF 3 shell at least partially surrounding the solid transition metal.

17. The method of claim 16, wherein the treating comprises dispersing the solid transition metal in an aqueous solution of hydrazine hydrate and contacting the solid transition metal with an aqueous solution of lanthanum ions and fluoride ions.

18. The method of claim 17, wherein the aqueous solution of lanthanum ions and fluoride ions comprises lanthanum nitrate hexahydrate and sodium fluoride.

19. The method of claim 16, wherein the treating comprises RF sputtering LaF3 onto the solid transition metal.

20. The method of claim 16, wherein the solid transition metal comprises bismuth, lead, copper, or a combination thereof.

Citation Information

Patent Citations

  • Composite electrode materials for fluoride-ion electrochemical cells

    US11251420B2

  • Non-aqueous fluoride salts, solutions, and their uses

    US20170062874A1

  • Nanostructural designs for electrode materials of fluoride ion batteries

    US20190372111A1

  • Electroactive materials modified with molecular thin film shell

    US20200185722A1

  • Fuel cell comprising at least two stacked printed circuit boards with a plurality of interconnected fuel cell units

    CN103620842A